GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2018)
A dataset containing 1018983021 species occurrences available in GBIF matching the query: BasisOfRecord: Observation or Machine Observation or Human Observation or Material sample or Literature Occurrence or Specimen or Fossil or Living Specimen or Unknown evidence. The dataset includes 1018983021 records from 10000 constituent datasets: 1934 records from Fig 14. Pollen profile from sediment core Schmiecher See. 80 records from Nannofossil abundance of Hole 37-333A. 54 records from Planktic foraminifera abundance of Hole 27-259. 3971 records from NMU Mammal Collection (Arctos). 6 records from Species diversity of Rhinebothrium Linton, 1890 (Eucestoda: Rhinebothriidea) from Styracura (Myliobatiformes: Potamotrygonidae), including the description of a new species. 56 records from Black grouse lek survey in Moray and Nairn 2009. 1582 records from Catalogue Lhomme 1923-[1963]. 5 records from A new genus and species of Sclerodactylidae (Echinodermata: Holothuroidea: Sclerothyoninae) from the Pacific coast of Panama, and assignment of Neopentamera anexigua to Sclerothyoninae. 396 records from (Appendix 1) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD95-2042. 98 records from Dörnberg. 46096 records from Herpetology Collection. 404 records from The Crematogaster (Hymenoptera, Formicidae, Myrmicinae) of Costa Rica.. 592 records from (Table 7) Ranges of benthic foraminifers through the Oligocene in DSDP Hole 26-253. 136 records from Bean geese on the Slamannan Plateau, Central Scotland between 1993 and 1995. 4 records from Arthropoden aus südotsalpinen Höhlen gesammelt von Karl Strasser. 4. Aufsatz. 2 records from Nouveautes sur la faune des Chilopodes de Yougoslavie. 174413 records from URM - Herbário Pe. Camille Torrand. 2 records from Macrozoque hoplandrioides (Coleoptera: Staphylinidae: Aleocharinae), a new genus and species of false Lomechusini from México. 1080 records from Streamlining the use of BOLD specimen data to record species distributions: a case study with ten Nearctic species of Microgastrinae (Hymenoptera: Braconidae). 2536 records from Antarctic Krill occurrence data from US AMLR "US Antarctic Marine Living Resources" Program. 6 records from Species of Wadicosa (Araneae, Lycosidae): a new species close to W. quadrifera (Gravely) from the Western Ghats, India. 670 records from Phytoplankton abundance at bottle station A3/66A. 12556 records from ZMMU MSU, White Sea Branch. 400 records from Range table from benthic foraminifers in ODP Hole 149-900A. 396 records from Plasm bearing foraminifera counts of multinet M21/1_MSN613. 15 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B2_820-4. 3804 records from (Appendix A) Ostracod taxa from IODP Site 306-U1314. 64 records from Freshwater Gwyniad Survey Data. 71 records from Review of the Poecilimon (Poecilimon) zonatus species group and description of new species from Turkey with data on bioacoustics and morphology (Orthoptera: Phaneropterinae). 56 records from Nannofossil abundance of Hole 10-85. 55 records from A revision of the New Zealand weevil genus Irenimus Pascoe, 1876 (Coleoptera: Curculionidae: Entiminae). 492 records from Rotifers of Macquarie Island. 12 records from The genus Thelepus Leuckart, 1849 (Annelida, Thelepodidae) in Brazil, with a redescription of the holotype of T. setosus (Quatrefages, 1866). 1 records from Rediscovery of Terebratulina austroamericana Zezina, 1981 (Brachiopoda: Cancellothyrididae) from off northern Chile. 4 records from A new diminutive sisorid catfish (Actinopterygii: Siluriformes) from northeastern India. 22 records from Allopatric color forms of Scaphidium morimotoi Löbl, 1982 (Coleoptera, Staphylinidae, Scaphidiinae) endemic to the Amami Islands, the Ryukyus, Japan. 74 records from Revisionary systematics of the endemic soft coral fauna (Octocorallia: Alcyonacea: Alcyoniina) of the Agulhas Bioregion, South Africa. 30 records from Three species of Reteporella (Bryozoa: Cheilostomata) in a diapiric and mud volcano field of the Gulf of Cádiz, with the description of Reteporella victori n. sp. 936 records from (Table 1) Distribution of calcareous nannofossils at ODP Hole 125-781A. 1496 records from Bulau. 159 records from (Appendix C) Benthic foraminiferal census data for extinction, uniserial survivor and high-flux, low-oxygen tolerant groups for ODP Hole 160-967A. 176 records from Great Crested Newt Special Area of Conservation (SAC) Monitoring Data. 3268 records from ZUEC-ARA - Coleção de Aracnideos do Museu de Zoologia da UNICAMP. 179374 records from PACA-AGP - Herbarium Anchieta. 800 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB04 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates. 70 records from The ant genus Tetraponera in the Afrotropical region: the T. grandidieri group (Hymenoptera: Formicidae).. 3970 records from Percentages of planktonic foraminifera species in sediment core RC24-27. 19034 records from 2010-2013 Beetle Data from Machair LIFE+ Project Plots. 535 records from Range table from planktonic foraminifers in ODP Hole 182-1134A. 120060214 records from Artportalen (Swedish Species Observation System). 100 records from Catalogue of distribution of lizards (Reptilia: Squamata) from the Brazilian Amazonia. IV. Alopoglossidae, Gymnophthalmidae. 346 records from Nannofossil abundance of Hole 28-265. 20 records from Description of three new troglobiontic species of Cybaeodes (Araneae, Liocranidae) endemic to the Iberian Peninsula. 339 records from Total foraminifera counts of multinet M10/2_MSN334. 19920 records from Vascular Plants Collection of National Museum of Nature and Science. 48 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/324-1. 12 records from A new species of Sextonia Chevreux, 1920 (Crustacea: Amphipoda: Liljeborgiidae) from the Okhotsk Sea. 4268 records from Free-living marine Nematodes from Ali, Rada Tilly and El Limite sandy beaches (Chubut, Argentina) 2006.. 53418 records from List of the specimens of the Vanuatu National Herbarium (PVNH). 343 records from Occurrence of mammalia relicts at site Felsställe. 14128 records from SEWBReC Grasshoppers, Bush-crickets and allies (South East Wales). 88 records from Range table from planktonic foraminifers in ODP Hole 172-1063A. 1382 records from Barcant Butterfly Collection - Lycaenidae. 83 records from Planktic foraminifera abundance of Hole 40-361. 58 records from Hypostomus velhochico, a new keeled Hypostomus Lacépède, 1803 (Siluriformes: Loricariidae) from the rio São Francisco basin in Brazil. 31 records from Two new species of Eretmocerus Haldeman (Hymenoptera: Aphelinidae) parasitizing Aleurolobus rhododendri Takahashi and Dialeuropora decempunctata (Quaintance & Baker) (Hemiptera: Aleyrodidae) from Taiwan. 1251 records from Loup 2016 présence occasionnelle communale (réseau Loup-Lynx ONCFS). 20534 records from Bruce Bennett Herbarium (BABY). 1976 records from Managing open habitats for species conservation: the role of wild ungulate grazing, small-scale disturbances, and scale - Corynephorus canescens domiated grassland. 298 records from Fig. 7 (right) Macrofossil concentrations in core Lz1104-5. 192 records from (Table 5) Planktonic foraminifera genera assemblage at DSDP Hole 80-548A. 44 records from Description of the larvae and pupae of eight species of the tribe Sitonini Gistel, 1848 (Coleoptera, Curculionidae) from Central Europe. 32 records from Proposal of Kupiuka and Plesiopiuka, two new genera of jumping spiders from Brazil (Araneae: Salticidae: Heliophaninae). 895 records from Códigos de barras de hongos ectomicorrízicos de localidades selectas del neotrópico mexicano. 101 records from The genus Setodes Rambur (Trichoptera, Leptoceridae) in Japan. 22784 records from Danish Plant Bugs (Miridae). 31 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 1998. 37142 records from ZUEC-POL - Coleção de Polychaeta do Museu de Zoologia da UNICAMP. 1093 records from Planktic foraminifera counts of sediment core V23-100. 86586 records from Données naturalistes d'Olivier ESCUDER. 71 records from Morphology and taxonomy of the orb-weaving spider genus Mecynogea, and a peculiar species of Argiope (Araneae, Araneidae). 54 records from Two new dragonflies (Odonata: Anisoptera) from the Miocene of Carinthia (Austria). 442 records from Abundance of planktic foraminifera at CTD station M39/4_404CTD-57. 12 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-1998-MNB6. 10230 records from Vascular plant specimens of Iida City Museum. 81 records from Nannofossil abundance of Hole 16-155. 3 records from Three New Spiders of the Families Clubionidae, Liocranidae and Gnaphosidae (Arachnida, Araneae) from Vietnam. 111 records from Nematode densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC02. 456 records from Late Pleistocene planktonic foraminifera of Hole 302-M0004C (Addendum 1). 124 records from Revision of early taxa of Australian gall midges (Diptera: Cecidomyiidae). 106 records from Fonoteca Zoológica, Museo Nacional de Ciencias Naturales, Madrid: FZ_REPTILIA. 44930 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Ornithology National Collection (MACNOr). 513 records from Planktic foraminifera counts of sediment core RC11-126. 36 records from Revision of the genus Centrophorus (Squaliformes: Centrophoridae): Part 2 - Description of two new species of Centrophorus and clarification of the status of Centrophorus lusitanicus Barbosa du Bocage & de Brito Capello, 1864. 336 records from Zielbach (Töll). 62 records from Notes on the genus Conocephalus Thunberg, 1815 (Orthoptera: Tettigoniidae: Conocephalinae) in Southwest China with description of one new species. 141 records from BIRDRACE Emslandracer. 8 records from Invasive non-native species records from SEWeb. 1402 records from SEWBReC Worms (South East Wales). 60 records from Revision of Hestiasulini Giglio-Tos, 1915 stat. rev. (Insecta: Mantodea: Hymenopodidae) of Borneo, with description of new taxa and comments on the taxonomy of the tribe. 333 records from Foraminifera species abundances from tow TT007_12-MOC21. 318 records from Measurements of elephant tusk trophies taken in Botswana 2003. 5969 records from Lichens of Knyszyn Forest. 255993 records from UMMZ Mammal Collection. 46318 records from Banco de datos florísticos del Herbario CHAP. 42 records from Record of 7 acritarch taxa from the Miocene, Pliocene and Pleistocene of ODP Hole 151-910C. 8 records from Redescription of Micaria beaufortia (Araneae, Gnaphosidae), with notes on Afrotropical Micaria. 4344 records from (Table 10) Distribution of Pleistocene to late Miocene nannofossils in ODP Hole 108-664A. 4104 records from Angelo State Natural History Collections (ASNHC) - Ornithology Collection. 5913 records from Données CardObs (hors programme spécifique). 18528 records from Big Island Invasive Species Committee - Pest Reports - 2005-2010. 48 records from Occurrence of mammalia relicts at site Groß-Rohrheim. 6959 records from Bird collection NTNU University Museum. 381 records from Bases de datos de plantas, insectos, reptiles, anfibios, aves y mamíferos del “Arroyo la Junta, Una joya de biodiversidad en la Reserva de la Biosfera Sierra La Laguna”. 858 records from Relative abundance of planktonic foraminifera in sediment core L-66. 22338 records from Akita Prefectural Museum, Hiroki Watanabe Collection. 198 records from Newhaven Sanctuary observations. 2 records from Review of the ant genus Nesomyrmex (Hymenoptera: Formicidae: Myrmicinae) in southern Africa.. 80505 records from Herbario Pontificia Universidad Javeriana. 228890 records from Inventaire National du Patrimoine Naturel : Enquête carnivores. 362 records from Colección Ornitológica Museo de Ciencias Naturales “Lorenzo Scaglia" (MMPOr) Mar del Plata, Argentina.. 42 records from The genus Cryptotendipes Beck et Beck in Florida, with the description of a new species (Diptera: Chironomidae: Chironominae). 195 records from Occurrence of mammalia relicts at site Vogelherd/Lonetal. 25944 records from Insect specimens of Komatsu City Museum. 233 records from (Appendix A) Planktonic foraminifera abundances in ODP Site 138-852B. 55155 records from HEPH - Herbário Ezechias Paulo Heringer. 46 records from Schulgarten der Hainbuchenschule (Hagenbach). 228 records from (Table 1.2.2.1) Integrated abundance of sympagic meiofauna in sea-ice cores of Polarstern cruise ANT-XXIII/7. 12347 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Ichthyology National Collection (MACNIct). 120 records from Plasm bearing foraminifera counts of multinet M21/5_MSN733. 59 records from Schulhofuntersuchung Thomas-Mann-OS. 790 records from Ostracode ratios of adult single valves to adult specimens in surface sediment samples from the Persian Gulf (Table 1b). 45622 records from ARC-PPRI: National Collection Of Fungi(1817-2009). 41 records from Analyses of the recent components in the sand fraction of sediment core PS1013-1. 1436 records from Range table from benthic foraminifers in ODP Hole 146-888B. 4 records from First record of Isegama Krombein (Hymenoptera, Chrysididae, Amiseginae) from China, with description of a new species. 2 records from A new species in the Simulium vernum group from the Alps of southern Germany: Simulium arminii (Diptera: Simuliidae). 10 records from On the spider genus Arboricaria with the description of a new species (Araneae, Gnaphosidae). 16 records from Mesene Doubleday (Lepidoptera: Riodinidae) from Parque Nacional da Serra do Divisor, Acre, Brazil, with taxonomic notes and the description of a new species. 1446 records from Planktic foraminifera abundance of Hole 74-525A. 283 records from Foraminifera species abundances from tow TT007_8-MOC15. 13894 records from University of Amsterdam (NL) - Páramo vegetation research, Central Andean Cordillera - Colombia. 44 records from Ptyctimous mites (Acari, Oribatida) of Victoria (Australia). 2025 records from Deforestación y fragmentación del hábitat: consecuencias ecológicas sobre la fauna de mamíferos de la selva tropical estacional. 57 records from NSG Hellbachtal. 4 records from A new species of Prosopistoma Latreille, 1833 (Ephemeroptera: Prosopistomatidae) from South India. 4 records from Simpsonichthys radiosus sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual killifish from the upper Rio Tocantins basin, central Brazil.. 6331 records from Benthic foraminifera of sediment core MD99-2286. 300 records from Census of Cnidaria (Medusozoa) and Ctenophora from South American marine waters. 15746 records from CMC_herpetology_vouchers. 107 records from Notoaturine water mites from New Zealand (Acari: Hydrachnidia: Notoaturinae) with the description of five new species. 1492 records from The communities of terrestrial macrofungi in different forest types of boreal zone in West Siberia. 204485 records from Waarnemingen.be - Non-native plant occurrences in Flanders and the Brussels Capital Region, Belgium. 6 records from Resolution of the types, diagnostic features, and distribution of two easily confused Sand Lizards, Pedioplanis laticeps (Smith, 1845) and P. burchelli (Duméril & Bibron, 1839) (Squamata: Lacertidae). 50 records from Ostracoda abundance of Hole 48-404. 1464 records from Colección Mastozoológica de la Universidad Industrial de Santander. 98 records from Occurrence of mammalia relicts at site Jaskinia Niedwiedzia. 34 records from Microzooplankton abundance and biomass at station NBP97-08-03-3. 10 records from Two new species of the genus Habrobathynella Schminke, 1973 (Syncarida, Parabathynellidae) from the southwestern peninsular India. 50 records from Banco de Germoplasma de la Universidad de Salamanca. 4 records from First record of Pyramica baudueri (EMERY, 1875) (Hymenoptera: Formicidae) from Bulgaria.. 1168 records from Registro de murciélagos del Cañón del Chicamocha, Santander (2013 - 2014). 84 records from Planktic foraminifera counts of sediment core ELT48.022-PC. 99 records from Plasm bearing foraminifera counts of multinet POS231/3_MSN1329. 68 records from Description of the first Palaearctic species of Tineobius Ashmead, 1896 with DNA data, a checklist of world species, and nomenclatural changes in Eupelmidae (Hymenoptera, Chalcidoidea). 2173450 records from Observations floristiques floutées issues de la base de données flore du Conservatoire botanique national alpin. 288 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 189-1172A. 6 records from Three new Macropsini (Hemiptera: Cicadellidae) leafhopper species from Australia. 2 records from Zetes latipes. 143 records from Planktic foraminifera counts at CTD station PS55/019. 19153 records from Ibaraki Nature Museum, Lichen collection. 14226 records from Primera fase de actualización de la Colección de Siphonaptera Alfredo Barrera del Museo de Zoología Alfonso Herrera. 186 records from Total foraminifera counts of multinet M21/4_MSN705. 794 records from Données naturalistes du Comité départemental de l'Essonne (CODEP91) de la Fédération Française d'Etudes et de Sports Sous-Marins. 20327 records from Herbier du Muséum d'Angers. 80889 records from Standing Waters Database - Scotland. 4578 records from Specimen records of spiders (Arachnida: Araneae) by monthly census for 3 years in forest areas of Yakushima Island, Japan. 116 records from Abundance of living benthic foraminifera in sediment core CD86_08_BC5. 1128 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB01 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates. 750 records from Small mammal species list 08. 33 records from Relative abundance of Florisphaera profunda in ODP Hole 121-758C. 4600 records from (Table 2) Distribution of calcareous nannofossils in ODP Hole 119-738C. 738 records from Correlación entre las condiciones ambientales y la pesquería de anchoveta a lo largo de la costa de Baja California. 13132 records from CABI Lepidoptera Collection. 20 records from (Table 1) Occurrences of ostracodes in ODP Hole 122-761B. 248124 records from University of Guelph Insect Collection (DEBU). 162 records from Plasm bearing foraminifera counts of multinet M21/2_MSN629. 100 records from Junge Heide, Radebeul/Dresden. 1950 records from ant-plant_symbioses. 8714 records from Bird Records held by Greater Manchester Ecology Unit. 551 records from Brood cell No. of trap-nesting species Alb 2008. 38 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 4846 records from SSNATV_2017_12_18. 6 records from New findings of Hexalona-branch representatives in Brazil, with a description of Prenda gen. nov. (Crustacea: Anomopoda: Aloninae). 467 records from Données naturalistes (Rhopalocères et Zygènes) de Benoit DUHAZÉ (CEN Aquitaine). 190 records from Überschwemmungsgebiet der Wied. 318 records from Size of planktic foraminifera at CTD station PS55/018. 4818 records from Birds (GMBO-BI). 854 records from Phytoplankton abundance during Lev Titov cruise LT91. 270 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1378. 198 records from Ant-like stone beetles on the roof of the world. Cephenniini of Nepal and Bhutan (Coleoptera, Staphylinidae, Scydmaeninae). 90 records from On the taxonomy of the genera Planovalvata Dubatolov & Kishida, Stigmatophora Staudinger and Pseudomiltochrista Dubatolov & Bucsek, with description of one new species (Lepidoptera, Erebidae, Arctiinae, Lithosiini). 1072 records from Percentages of planktonic foraminifera species in sediment core V30-49. 1420 records from Natural England Bat Records for Berkshire and Oxfordshire (Held by Thames Valley Environmental Records Centre). 42 records from (Table 2) Major nannofossil abundances in three Leg 194 site survey gravity cores. 8 records from Analyses of the recent components of sediment core PS1275-1. 178 records from Birdrace-Team_Wangerooge-Friesland. 100970 records from Canadian Museum of Nature Bird Collection. 10 records from New taxa and notes of katydids from the tribe Meconematini (Orthoptera: Meconematinae) from Brunei Darussalam (Part 2). 16 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/313-1. 6 records from Cyrtodesmus baerti, n. sp., a cryptic millipede from the Galápagos Islands, Ecuador (Diplopoda, Polydesmida, Cyrtodesmidae). 994 records from Especies de Leptohyphes (Insecta: Ephemeroptera: Leptohyphidae) del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 2516 records from CMC_ornithology_GRC. 2904 records from (Table 4) Distribution of Pleistocene to early Pliocene nannofossils in ODP Hole 108-658A. 13632 records from English Nature Oxfordshire Invertebrate Surveys. 10 records from Three new species of Lyssomanes HENTZ, 1845 from Peru (Arachnida: Araneae: Salticidae). 2 records from Orthochaetes estrelanus sp. n., a new species from northern Portugal and new records of other Styphlini (Coleoptera, Curculionidae).. 20 records from Microzooplankton abundance and biomass at station TT050_24-12. 4014 records from Fungi and Lichens, Outer Hebrides. 500 records from Plant specimens of Oiso Municipal Museum. 9262 records from (Supplement 1) Relative abundance of planktic foraminifera in sediments of the last 560 kyr of ODP Hole 165-999A, Caribbean Sea. 1192 records from Planktic foraminifera counts of sediment core V22-196. 344 records from (Table T3) Planktonic foraminifera stratigraphy of ODP Hole 198-1209A, Zones P5-P6b. 4260 records from database_hemiptera. 86 records from bmhs_beetle_collection. 7 records from Abundance of nematoda in sediment profile M3/1_012 from the Iberian deep sea basin (Table 5). 16 records from Three new species of seasonal killifishes of the Simpsonichthys antenori species group (Teleostei: Cyprinodontiformes: Rivulidae) from the rio São Francisco basin, Brazil.. 253 records from Range table from planktonic foraminifers in ODP Hole 139-858A. 279284 records from Mississippi Entomological Museum. 602 records from Planktic foraminifera abundance of Hole 9-82. 1477 records from Nannofossil abundance of Hole 30-287. 910 records from GERECO_Environnement_2017_12_18. 336 records from (Table 4) Distribution of recurrent benthic foraminifera at DSDP Hole 75-530A, from Campanian and Maestrichtian. 114 records from Schulgarten Fichteschule. 16 records from The spiny theridiid genus Meotipa Simon, 1895 in India, with description of a strange new species with translucent abdomen and a phylogenetic analysis about the genus placement (Araneae, Theridiidae). 890 records from Molluscs in surface sediments off Sylt collected during HEINCKE cruise HE262. 106 records from On the taxonomy of southern South American species of the wolf spider genus Allocosa (Araneae: Lycosidae: Allocosinae). 56 records from Meiofauna abundance in sediment core 13077-021. 5 records from A new species of Rhigognostis (Lepidoptera, Plutellidae) from the Canary Islands. 26263 records from The Orthoptera collection (EO) of the Muséum national d'Histoire naturelle (MNHN - Paris). 235725 records from AM: Freshwater Invertebrates (1900-2005). 38169 records from Time slice 2 of planktic foraminifera of the last glacial maximum. 24 records from An inordinate fondness for Osedax (Siboglinidae: Annelida): Fourteen new species of bone worms from California. 1040 records from Foraminifera and ostracods profile from sediment core AV14_K2-3. 10 records from A new Candonopsini (Ostracoda) genus from subterranean waters of New South Wales (Australia). 5088 records from Freshwater fishes of Greece. 2955 records from Distribution of major planktic foraminifer at Site 177-1092. 42 records from Studies in Guatemalan Ensifera: New Glaphyrosoma species (Orthoptera: Anostostomatidae) and additional data for other described species. 133 records from Foraminifera species abundances from tow TT011_15-MOC78. 4 records from A remarkable new plant bug genus and species (Hemiptera, Heteroptera, Miridae, Deraocorinae) from the Australian wet tropics. 70 records from Benthic foraminifera abundance of Hole 56-434. 6 records from Callianassa ehsani, a new species of Callianassidae (Crustacea, Decapoda, Axiidea) from Gulf of Oman, Iran. 8 records from Planktic foraminifera abundance of Hole 23-225. 158 records from Planktic foraminifera counts of sediment core V19-204. 90 records from New species of Hercostomus Loew, 1857 (Dolichopodidae, Diptera) from Japan. 2012 records from Caracterización morfométrica del bagre rayado para la cuenca del Magdalena. 837 records from Colección de Zoología Invertebrados - Carcinología. 1689 records from Antarctic Marine Protists species checklist. 3947 records from Herbario del Jardín Botánico-Histórico La Concepción: HBC. 14 records from Three new species of phytoseiid mites (Acari: Phytoseiidae) from Bahia State, Brazil. 7208 records from Records from the RHS insect reference collection. 530 records from Les mollusques terrestres de la faune de Corse : Mission 1996 de Theo RIPKEN. Muséum national d'Histoire naturelle, Paris et DIREN Corse. 6 records from Two new eriophyoid mite species (Trombidiformes: Eriophyoidea) from the cocoa tree, and a note on Shevtchenkella biseta (Nalepa). 42 records from Five new species of Stenochrus (Schizomida: Hubbardiidae) from Oaxaca, Mexico. 330 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-17. 378 records from Nannofossil abundance of Hole 9-77B. 3367 records from Base de datos del Municipio General Heliodoro Castillo, Guerrero (120. Sierra Madre del Sur). 160 records from Occurrence of mammalia relicts at site Lespezi-Lutarie. 261 records from (Table 2) Occurrence and estimated abundance of planktonic foraminifers at DSDP Hole 85-571. 20 records from Données naturalistes de Jean-Patrick Le Duc. 9 records from Occurrence of mammalia relicts at site Conturines Höhle. 20 records from Planktic foraminifera abundance of Hole 6-47A. 3669 records from ARKO strandeng. 2 records from Celaeno obsoleta. 290 records from (Table 2) Planktonic foraminifer species distribution, abundance, and preservation in DSDP Site 92-597. 184 records from Nannofossil abundance of Hole 11-106. 9 records from Miltochrista wangmini, a new species from China (Lepidoptera, Erebidae, Arctiinae). 3984 records from Fungal Collection of Natural History Museum and Institute, Chiba. 24 records from Description of lithologic section units of IODP Hole 325-M0049B. 21 records from First record of Psilacrum Becker 1912 (Chloropidae, Diptera) from Brazil, with the description of a new species. 23182 records from Cercle des mycologues de Montréal Fungarium (CMMF). 2816 records from (Table 2) Distribution of Campanian-Maestrichtian agglutinated foraminifers in DSDP Hole 78-543A. 274 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/038-3. 68 records from New records in vascular plants alien to Kyrgyzstan. 824020 records from CRBPO : STOC, Baguage. 6 records from Aquatic microdrile Oligochaeta (Annelida, Clitellata): New nominal taxa and combinations since 1984. 438 records from South East Scotland Tetrad Atlas 1988 - 1994 - sensitive breeding species. 464 records from Vorderer Tiergarten (Dessau). 24 records from Kindergarten. 5452 records from Systematic census of the private plantations of the firewood of the Benin .. 699 records from Colección Mastozoológica Universidad de los Llanos. 137360 records from CSIC-Real Jardín Botánico-Colección de Hongos (MA-Fungi). 29482 records from Mosses and Liverworts: Records for Kent.. 585 records from (Table T2) Calcareous nannofossil stratigraphy in ODP Hole 186-1151C sediments. 103072 records from USGS South Florida Fish and Invertebrate Assessment Network Crustaceans. 173714 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 96 records from SNH Invertebrate Site Condition Monitoring 2015: Tweedwood - Gateheugh SSSI. 24 records from Benthic macrofauna abundance of sediment core 12930-068. 339 records from iHerbarium. 108 records from Jeff Ogden Collection. 23 records from Planktonic foraminifera in ODP Hole 112-688A (Table 1). 67 records from Neostasina gen. nov., a new genus of huntsman spiders from the Neotropical region (Araneae, Sparassidae, Sparianthinae). 140 records from A new species and new country records for the genus Leptobium Casey in the Palaearctic Region (Coleoptera: Staphylinidae: Paederinae). 30246 records from Données "faune" de la Société Nationale de Protection de la Nature (SNPN) pour le SINP île de France. 11 records from Nematomorpha from Hong Kong and description of a new species from Malaysia. 81 records from Abundance of benthos infauna at station GIK23013-2. 6 records from Isoperla vjosae sp. n., a new species of the Isoperla tripartita group from Albania (Plecoptera: Perlodidae). 114 records from Mauervegetation,Flechten und anderes. 674 records from Feriendorf des Kreises Groß-Gerau Ober-Seemen/Gedern. 362 records from New data on spiders (Aranei) from the Maritime Province, Russian Far East. 33 records from Range table from benthic foraminifers in ODP Hole 139-858D. 218 records from In situ observations of Stygiomedusa gigantea. 96726 records from Buffalo Society of Natural Sciences Clinton Herbarium. 2 records from Schistobrachia kabata sp. nov. (Siphonostomatoida: Lernaeopodidae) from rajiform hosts off South Africa. 6478 records from Arthropods from Praia da Vitória (Terceira, Azores, Portugal). 38 records from Antarctic Krill occurrence data from Japanese expeditions. 2 records from Trachelus stipa (Hymenoptera: Cephidae), a new stem sawfly from Central Anatolia associated with feather grass (Stipa holosericea, Poaceae). 17828 records from Balsfjord Nature Reserves. 64 records from Revision of the Barsine cardinalis - anomala ' species-complex' (Lepidoptera, Erebidae, Arctiinae). 50 records from Université Pédagogique Nationale de Kinshasa (UPN). Plantes phytosanitaires. - Projet CABIN. 45 records from A checklist of the Iranian Mordellidae (Coleoptera: Tenebrionoidea). 19 records from Analyses of the recent components of sediment core PS1401-2. 113 records from verschiedene Kleingewässer um Oldenburg/Holstein. 39876 records from CNIN/Thysanoptera. 302 records from Molluscan fauna of Gueishan Island of Taiwan. 1768 records from (Table 7) Distribution of dead benthic foraminifera in deep-sea surface sediments of the Scotia Sea, part 1. 68 records from Species delimitation in the Gehyra nana (Squamata: Gekkonidae) complex: cryptic and divergent morphological evolution in the Australian Monsoonal Tropics, with the description of four new species. 4332 records from Prime Hoverfly (Insecta: Diptera: Syrphidae) Areas (PHA) as a conservation tool in Serbia. 5936 records from John Clayton's Fijian Moth Collection. 87 records from The genus Phlesirtes Bolivar, 1922 (Orthoptera: Tettigoniidae: Conocephalinae, Conocephalini; Karniellina), a review of the genus with data on its bioacoustics and the description of new species. 5940 records from Data mobilized by the National Herbarium of Benin in the framework of the JRS Biodiversity project of Benin. 314 records from (Table 3) Planktonic foraminifer species distribution, abundance, and preservation in DSDP Hole 92-598. 2479 records from Siliceous microfossil occurrence, Site 177-1088. 1031 records from (Appendix 6) Benthic foraminifera at termination II in sediment core PS1906-2 in the Greenland Sea. 4778 records from PAMP-tracheo: Vascular plants in Pamplona Basin (Navarra, Spain). Undergraduate thesis, D. Vicente. 1196 records from Insect Ichneumon fly (KIDR-IN). 122 records from BIRDRACE Kollektiv Eisente. 54066 records from Fishes in MZNA-VERT: cyprinid and salmonid communities in the rivers Erro and Urederra (Spain). PhD project, Cristina García-Fresca. 882 records from Diatom abundance measured on water bottle samples at station PS58/107-5. 3006 records from Mammal records captured from Licence Returns submitted to Natural Resources Wales. 6 records from A new species of sponge-dwelling Elacatinus (Pisces: Gobiidae) from the western Caribbean.. 324 records from Nannofossil abundance of Hole 15-150. 121374 records from DBG Kathryn Kalmbach Herbarium. 67810 records from Insect specimens of Tochigi Prefectural Museum. 3402 records from MfN Fish Collection, Zoology. 1492 records from SEWBReC Slime Molds (South East Wales). 320 records from Bases de datos de Tanaidaceos (Crustacea: Peracarida) del Mar Caribe mexicano y Poliquetos pelágicos del Golfo de México y Mar Caribe mexicano. 525 records from (Table 5) Carbon flux, paleoproductivity, relative abundance of foraminifera on sediment core PS2138-1. 3104 records from Bulk components and planktonic foraminifera of sediment core GeoB7139-2. 9 records from A new skipper from China: Notocrypta ariannae n. sp. (Lepidoptera, Hesperiidae). 20 records from Supplement to the knowledge of the genus Batraxis Reitter (Coleoptera: Staphylinidae: Pselaphinae) of China. 152 records from Phytoplankton abundance at station Rigel_1_2005-07 in July 2005, Chipana, Chile. 3790 records from Inventaire des Lépidoptères Rhopalocères et Zygènes de France métropolitaine. 2 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 364 records from Total foraminifera counts from M35/1_MSN1060. 27140 records from Royal Botanical Gardens Herbarium. 21381 records from MEXU/Asclepiadaceae. 316 records from (Table 2) Distribution of planktonic foraminiferal tests in sediments from Core ML7_475. 51184 records from Herbarium Amazonense. 280006 records from Vascular plant herbarium, NTNU University Museum. 12 records from A new genus of katydid from the Amazon Rainforest (Orthoptera: Tettigoniidae; Phaneropterinae; Steirodontini): Ninth contribution to the suprageneric organization of the Neotropical phaneropterines. 11634 records from Diversité des Poissons de Nouvelle-Calédonie, pêche à la roténone. 23576 records from Records of the Australian National Botanic Gardens Seedbank. 36 records from Two new fish species of the genus Puntius Hamilton (Cyprinidae) from Manipur, India, with notes on P. ticto (Hamilton) and P. stoliczkanus (Day).. 648 records from Parc_Naturel_Régional_des_Préalpes_d'Azur_2017_12_18. 9716 records from Nature Conservancy Council Berkshire Meadows Survey 1984-87 (as held by Thames Valley Environmental Records Centre). 30 records from A new genus and four new species of subfamily Cyclocypridinae (Crustacea, Ostracoda) from Thailand. 4 records from A new species of Synotaxus and the first chromosomal study on Synotaxidae, presenting a rare XY sex chromosome system in spiders (Araneae, Araneoidea). 88 records from A review of the Callogobius (Teleostei: Gobiidae) from the Red Sea with the description of a new species. 6 records from A new species of the genus Gracixalus (Amphibia: Anura: Rhacophoridae) from Mount Jinggang, southeastern China. 420 records from Dinoflagellate cysts counted on two fractions of surface sediment samples from stations A-9 to A-39. 60 records from Descriptions of a new species and previously unknown males of Nesticus (Araneae: Nesticidae) from caves in Eastern North America, with comments on species rarity. 16 records from Potamonautes nheenae, a new species of freshwater crab from Gabon, Central Africa, with a description of the first known male of Erimetopus brazzae (A. Milne-Edwards, 1886) from the Democratic Republic of the Congo, Central Africa (Brachyura: Potamoidea: Potamonautidae). 286 records from Planktic foraminifera abundance of Hole 18-179. 680 records from Phytoplankton abundance measured on water bottle samples at station PS65/508-2. 163778 records from Coleoptera collection, NHM. 103317 records from Wicken Fen nature reserve species data held by The National Trust. 825 records from Planktic foraminifera counts at CTD station M39/4_352CTD-11. 480 records from Range table from benthic foraminifers in ODP Hole 172-1057B. 105 records from Phytoplankton abundance at station Sechin_2003-12-28_2, Casma, Peru. 722 records from SEWBReC Lacewings and Allies (South East Wales). 562 records from UWIZM International Lepidoptera Collection. 109 records from Foraminifera species abundances from tow TT011_3-MOC60. 3304 records from Proyecto de cultivo extensivo y comercialización de las mariposas de la región de Chajul, Chiapas. 492 records from Araignées PNRL-2010 (Troyon,Jezainville-pelouse, Genicourt-pelouse). 2268 records from Alterra (NL) - Microarthropods inventory in European countries. 98 records from New species and new records of gelechiid moths (Lepidoptera, Gelechiidae) from southern Siberia. 4 records from Range table from benthic foraminifers in ODP Hole 194-1193A. 6 records from New species of Poecilocloeus Bruner, 1910 (Orthoptera: Acrididae: Proctolabinae) from Paraná State, Brazil. 17 records from Assemblage of living benthic foraminifera in sediment core CD146_55918#7, >150 µm. 2 records from Deux especes nouvelles pour la science du genre Eupolybothrus Verhoeff (Lithobiomorpha: Ethopolinae). - Two new species for the science in the genus Eupolybothrus Verhoeff (Lithobiomorpha: Ethopolinae). 7938 records from (Table 3) Stratigraphic distribution of dinocyst taxa in ODP Hole 150-903C. 13488 records from Naturhistorisches Museum Mainz, Schmetterlingssammlung Rodenkirchen. 15800 records from English Nature Oxfordshire Chalk Grassland Survey. 308 records from Wildkräuter. 648 records from Données naturalistes de BALLUCK Cindy. 5 records from Microzooplankton abundance and biomass at station TT050_2-10. 288 records from Plasm bearing foraminifera counts of multinet M21/2_MSN650. 394 records from Berlin-Brandenburg Plant Collection 2004. 3522 records from Centro de Recuperación de Fauna Silvestre "La Tahonilla". Cabildo de Tenerife. 6 records from The mythic species Issus analis Brullé, 1833 (Hemiptera, Fulgoroidea, Issidae): still an enigmatic taxon. 2543 records from Foraminifera and stable isotopes of sediment core PS1754-1. 243 records from Total foraminifera counts of multinet M12/3_MSN560. 38 records from On the systematic position of the genera Paraplastis Hampson, Migoplastis Felder and Dondera Moore (Lepidoptera, Erebidae, Arctiinae). 1 records from Leptanillahypodracos sp. n., a new species of the cryptic ant genus Leptanilla (Hymenoptera, Formicidae) from Singapore, with new distribution data and an updated key to Oriental Leptanilla species. 36708 records from Hokkaido University Coleoptera Collection. 94 records from Microplankton abundance at Station MARCH-1998-GN36199804610MSB01 in the euphotic zone of the Aegean Sea in March 1998. Part 1 - diatoms. 94 records from Artenerfassung für Jedermann in der Grundschule Kirchboitzen. 38 records from New species of Bacuma Cameron (Hymenoptera: Braconidae: Braconinae) from Kenya and West Darfur with a key to species. 540 records from Registros biológicos de aves Distrito de Manejo Integrado Musichi y Santuario de Fauna y Flora los Flamencos, La Guajira.. 763 records from Freiburger GEO-Tag der Artenvielfalt. 18 records from (Tab. 14) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 32-307, Hawaiian Magnetic Lineations. 396 records from Tortue Olivâtre. Données publiées dans le cadre du projet JRS Bénin. 6 records from A new species of Enchytraeus (Enchytraeidae, Oligochaeta) from the profundal of Lake Van, the world's largest soda Lake (Turkey, East Anatolia). 71 records from Abundance and carbon biomass of phytoplankton at station TT008_5-CTD50. 266 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Parulidae. 41482 records from UMNH Birds Collection (Arctos). 12 records from Inventaire de la flore des espaces verts de la CREA avec le protocole Florilèges. 22 records from Range table from planktonic foraminifers in ODP Hole 182-1129B. 62424 records from bioman_belgium. 18 records from Bases de datos de plantas, insectos, reptiles, anfibios, aves y mamíferos del “Arroyo la Junta, Una joya de biodiversidad en la Reserva de la Biosfera Sierra La Laguna”. 10 records from Range table from planktonic foraminifers in ODP Hole 171-1049B. 40 records from A mountain of millipedes IV: Species of Prionopetalum Attems, 1909, from the Udzungwa Mountains, Tanzania. With notes on “ P. ” fasciatum (Attems, 1896) and a revised species key (Diplopoda, Spirostreptida, Odontopygidae). 2016 records from RECORD Freshwater Fish Data. 728 records from Palynology of profile Füramoos III. 38 records from Microplankton data off Chipana Bay, 2006, Chile. 22 records from GEO-Tag der Artenvielfalt der Klasse 7c am Gymnasium Allee im Wohlers Park. 1561 records from (Table 2) Relative abundances of benthic foraminifera in ODP Hole 128-798B. 78 records from A review of the Malagasy Pachypanchax (Teleostei: Cyprinodontiformes, Aplocheilidae), with descriptions of four new species.. 500 records from Colección de Mamíferos – Universidad de la Amazonia. 2 records from Hoplophora decumana. 4164 records from Vietnam Type Culture Collection. 501 records from Counts of benthos communities in Kongsfjorden in 2009. 28 records from Données naturalistes de Piotr DASZKIEWICZ. 290133 records from UAM Mammal Collection (Arctos). 3 records from Microplankton counts and carbon biomass at station TT008_4-TM3. 196 records from Afroneutria, a new spider genus of Afrotropical Ctenidae (Arachnida, Araneae). 442 records from Caracterización florística de las ciénagas en Gamarra y Barrancabermeja de 2012. 134 records from Range table from planktonic foraminifers in ODP Hole 141-861A. 52 records from Nanofaunaartenliste. 17 records from Taxonomy and distribution of Terebellides (Polychaeta: Trichobranchidae) in the northern South China Sea, with description of three new species. 16 records from Analyses of the recent components of sediment core PS1278-1. 4 records from Discovery of Penicillidmus in the Bismarck Archipelago, Papua New Guinea, with description of a new species from Lavongai (New Hanover) Island (Coleoptera, Staphylinidae, Scydmaeninae). 39402 records from Base de datos de la distribución de la flora de la Reserva de la Biosfera Tehuacán-Cuicatlán. 1490 records from Total foraminifera counts of multinet SO118_MSN1252. 6 records from New taxa of the Meganola argentescens (Hampson, 1895) species group from China (Lepidoptera, Nolidae, Nolinae). 49 records from Review of the genus Pityocona Meyrick, 1918 (Lepidoptera: Gelechiidae) in China, with descriptions of five new species. 144 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-960A. 664 records from The jumping lynx spider Oxyopes salticus Hentz, 1845 and its Neotropical relatives (Araneae: Oxyopidae). 2156 records from Fishes of the Congo River 2010 Expedition. 132 records from Nannofossil abundance of Hole 24-234. 113 records from Smear slide analysis on sediment core GeoB4212-2. 2 records from Synthèse de la Répartition des populations de cerf élaphe en 1988 (réseau Ongulés sauvages ONCFS-FNC-FDC). 52 records from Biología reproductiva de Hechtia schottii Baker ex Hemsley (Bromeliaceae), una especie dioica y rara de la Península de Yucatán. 6 records from Dinoflagellate abundance of Hole 85-572A. 1390 records from Distribution of planktic foraminifera and stable istopes of sediment core MSM05/5_712-2. 4 records from New data on the rare Afrotropical scarab beetles Orphnus drumonti Frolov and Delopleurus naviauxi Frolov et Cambefort (Coleoptera, Scarabaeidae, Orphninae and Scarabaeinae). 5936 records from Algae, Specimens, Agder naturmuseum (KMN). 19 records from Range table from planktonic foraminifers in ODP Hole 182-1129A. 3 records from Microplankton counts and carbon biomass at station TT011_9-CTD115. 2688 records from Florística y biogeografía de algunos bosques mesófilos de la Huasteca Hidalguense: Fase 3 (Chapulhuacán y Pisaflores). 384 records from Inventaire des Spongiaires des eaux peu profondes de la zone maritime du Parc National de la Guadeloupe (PNG). 16 records from Five new species of the damselfish genus Chromis (Perciformes: Labroidei: Pomacentridae) from deep coral reefs in the tropical western Pacific.. 462 records from (Figure 1f) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3175BC. 12 records from Relationships of the New World cichlid genus Hypsophrys Agassiz 1859 (Teleostei: Cichlidae), with diagnoses for the genus and its species.. 2 records from A century in synonymy: molecular and morphological evidence for the revalidation of Glyptosternon osсhanini (Herzenstein, 1889) (Actinopterygii: Sisoridae). 515 records from Dinoflagellate cysts from sediment core PS2741-1. 2318 records from (Fig. 5) Distribution of benthic foraminifera in sediment profile GeoB9526. 2 records from Planktic foraminifera abundance of Hole 28-274. 12108 records from Spécimens d'herbiers de G. Fenoul (FEN). 244 records from Megafauna abundance and biomass from trawl samples obtained during cruise DI237. 36 records from The Neotropical sharpshooter genus Ruppeliana Young (Insecta: Hemiptera: Cicadellidae): four new species, key to males, and new synonyms. 80312 records from R - Herbário do Museu Nacional. 56 records from Stadtpark Prinzengarten (Sigmaringen). 92558 records from The DNA and Sample Repository at AIT. 5810 records from Colección del Banco de Germoplasma de la Universitat de València. 399 records from Phytoplankton abundance at the sea bottom off Sechura in january 2007, Peru. 204 records from Plasm bearing foraminifera counts of multinet M21/5_MSN729. 2 records from Identification of Nipaecoccus (Hemiptera: Coccomorpha: Pseudococcidae) species in the United States, with descriptions of Nipaecoccus bromelicola sp. n. and the male of N. floridensis Beardsley. 242 records from GEO-Hauptveranstaltung Bodden (Vilm). 567 records from Foraminifera distribution of sediment core SDSE186. 111 records from Coccolith counts of multinet M32/5_MSN974. 3371 records from (Appendix A) Campanian-Maastrichtian calcareous nannofossils in DSDP Hole 44-390A. 40 records from Meiofauna abundance in sediment core 54301-009. 2 records from Nothrus pigerrimus. 345 records from (Table 2) Components of turbidite samples of ODP Leg 101 holes. 238854 records from UF FLMNH Ichthyology. 8 records from Herpetology Collection. 460 records from Pilularia Globulifera distribution map in Denmark. 2307 records from Nekton and plankton counts from RMT (4500 µm) hauls of cruise GAE 1975/76. 391 records from (Fig. 4) Nannofossil abundance of Cretaceous profile L´Arboudeysse, SE France. 522265 records from RECORD Vascular Plant Data. 2109 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during Friedrich Heincke cruise FHE238. 464 records from Benthic meiofauna abundance in surface sediment of core PLG93_BCORE2. 234 records from Total foraminifera counts of multinet M21/4_MSN695. 6126 records from NDFF Wall Plants Monitoring Program. 66 records from Deep sea Syllidae (Annelida, Phyllodocida) from Southwestern Atlantic. 50 records from (Table 1) Analyses of coarse fraction of DSDP Hole 94-609. 73 records from Meiofauna abundance in sediment core 12930-075. 4 records from On the taxonomic status of amphidromous shrimp Paratya borealis Volk, 1938 (Crustacea: Decapoda: Atyidae) from the south of the Russian Far East. 1079 records from (Table 7) Species composition of clusters, ODP Holes 139-856A and 139-857A. 118 records from Nannofossil abundance of Hole 3-20C. 4 records from Youngest representative of the extinct genus Microphorites in the Eocene amber of France (Diptera: Dolichopodidae: Microphorinae). 58 records from A new species of Jupiaba Zanata, 1997 (Ostariophysi, Characiformes, Characidae) from the rio Tocantins drainage, Brazil.. 386 records from Total foraminifera counts of multinet POS247/2_MSN1383. 105 records from (Table 11) Planktonic foraminifer abundance of ODP Hole 162-987A. 2303 records from Planktic foraminifera abundance in per cent of Hole PRAD1-2. 8 records from Planktic foraminifera abundance of Hole 23-223. 90 records from Abundance of three benthic foraminifera species in surface sediments of a North-eastern Atlantic Abyssal Locality. 2 records from A new black fly species of Simulium (Gomphostilbia) (Diptera: Simuliidae) from Taiwan, with keys to all 13 species of the Simulium varicorne species-group. 25 records from Hyolithen - SMF. 2 records from Murcia trimaculata. 164 records from Donación de la base de datos resultado del diagnóstico de la diversidad de maíces nativos, su agroecosistema y sus parientes silvestres presentes en Papigochic y su zona de influencia.. 196568 records from Données de l'Observatoire de la Faune de Bourgogne. 284 records from Three new species, Elathous zagrosensis sp. n., Zorochros dilatatus sp. n., and Dicronychus iranicus sp. n., and noteworthy records of click beetles from western Iran (Coleoptera: Elateridae). 192 records from Nematode abundance of the Eastern Mediterranean Sea in cold seep sediments collected during Maria S. Merain cruises MSM13/3 and MSM13/4 in 2009. 63 records from Nannofossil abundance of Hole 9-81. 4 records from A new species of the genus Oligodon Fitzinger, 1826 (Squamata: Colubridae) from Cu Lao Cham Islands, central Vietnam. 5184 records from ConDidact Citizen Science Surveys - Spiders 2014. 3 records from An annotated checklist of the psyllids of New Zealand (Hemiptera: Psylloidea). 214 records from vegoek. 87 records from Barsura Volynkin, Dubatolov & Kishida, gen. nov., with descriptions of three new species (Lepidoptera, Erebidae, Arctiinae). 712 records from Dinoflagellate abundance of Hole 94-607. 4725 records from Porifera MZS. 48 records from A new species of Bedotia (Teleostei: Atherinomorpha: Bedotiidae) from the Rianila drainage of Eastern Madagascar, with redescriptions of Bedotia madagascariensis and Bedotia geayi.. 31968 records from Herpetology. 130 records from Phytoplankton abundance at station Sechin_2003-07-15_1, Casma, Peru. 4 records from A new groundwater-dwelling species of Euryrhynchina from Cameroon (Malacostraca, Decapoda, Euryrhynchidae). 50 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station MARCH-1995-D4. 72 records from Ice Algae Barents Sea. 353 records from (Table 1) Fossil record of foraminifera and ostracoda from Albersdorf clay pit, north Germany. 46 records from A survey of East Palaearctic Gnaphosidae (Araneae). 5. On Synaphosus from Central Asia. 2502 records from MGC Herbarium of University of Malaga (Spain): MGC-Briof dataset. 5061 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise DeHolland1986. 20 records from Arachnid specimens of Okinawa Prefectural Museum & Art Museum. 181755 records from Marine Commercial Fish Survey (FV Kapala, FV Trader Horn, FV Shelley, FV Kirrawa, FV May Bell) in the East and South East Australian Region from 1975 to 2008. 31357 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Cryptogamic National Collection (BAc). 26 records from Five species of the genus Epicephala Meyrick, 1880 (Lepidoptera: Gracillariidae) from China. 618 records from Planktic foraminifera abundance of Hole 23-225. 378 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Podicipedidae. 70954 records from HBRG Vertebrates (not Badger) Dataset. 22 records from Genetic and morphological evidence for a new cryptic species of Ectinogonia (Coleoptera: Buprestidae) from central Chile. 56 records from Checklist of the freshwater snails (Mollusca: Gastropoda) of Mongolia. 2039 records from Collections de coquilles continentales du Muséum d'histoire naturelle de Grenoble. 1700 records from Visual Plants (144.41.33.158) - Botanical garden, University of Hohenheim, Germany. 6491 records from Les Rubiaceae, Orchidaceae, Moraceae, Sapindaceae, Malvaceae, Melastomataceae, Verbenaceae, Loganiaceae, Sapotaceae, Scrophulariaceae, Sterculiaceae, Liliaceae, Meliaceae, Ochnaceae, Tiliaceae, Rosaceae, Solanaceae, Violaceae, Zingiberaceae, Myrtaceae, Rutaceae, Loranthaceae et quelques 71 autres familles de plantes de l'Herbier du Centre National de Floristique en Côte d'Ivoire.. 104 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_5-CTD20. 2 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Sturnidae. 10 records from Troglocaris (Xiphocaridinella) kumistavi sp. nov., a new species of stygobiotic atyid shrimp (Crustacea: Decapoda: Atyidae) from Kumistavi Cave, Imereti, Western Georgia, Caucasus. 3422 records from Highland Breeding Bird Data 2002-2003 - non-sensitive breeding species. 100 records from Caracterización de la ornitofauna del Cerro Tacarcuna, Unguía, Chocó. 2222 records from (Table 15) Distribution of planktonic foraminifera in the early to early late Oligocene section of ODP Hole 149-900A. 372 records from Colección de Entomología - Arthropoda. 276 records from Mokihinui River Hydro Proposal. 67 records from Inventario Murciélagos Finca Naranjito, Aracal, Yopal, Casanare. 10 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, >125 µm fraction. 106 records from (Table 4b) Range chart of benthic and planktonic foraminifera of ODP Hole 127-796B. 264 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Fósseis (ZUFMS-FOS). 42470 records from Fish specimens of Bihoro Museum. 55 records from Seeufer ehem. BUGA-Gelände. 3459 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC12-294. 110 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Cragbank and Wolfehopelee SSSI. 910 records from Collection Lepidoptera SMF. 2187 records from (Table 2) Relative abundance of benthic foraminifera in sediment core HUD84-030-04. 1068 records from Leopard Seal census, Heard Island 1987/88. 12 records from Range table from benthic foraminifers in ODP Hole 178-1100D. 2378 records from kerkyra. 1 records from Description of a new Kempnyia Klapálek from Brazil (Plecoptera: Perlidae) with life stages associated using DNA barcodes. 138 records from Kinder- und Jugendferiendorf des Kreises Groß-Gerau - Gedern/Ober-Seemen. 2424 records from Foraminifera abundance of Hole 75-532B. 4137 records from Benthic foraminifera and nannofossil abundance of Hole 40-360. 130 records from Abundance of living benthic foraminifera in sediment core CD86_05_BC5. 28 records from The Apseudomorpha (Crustacea: Tanaidacea) of the Gulf of Cadiz and Horseshoe Continental Rise (NE Atlantic): A taxonomic review with new records, species, and ecological data. 6 records from On two Italian Lithobius species described by Silvestri, with taxonomic notes on the genus Eupolybothrus Verhoeff (Chilopoda, Lithobiida). 58 records from Brenz (Heidenheim). 26 records from Solomon Islands Ants 2015. 360 records from (Figure 1c) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3192. 390 records from Total foraminifera counts of multinet M21/6_MSN785. 415 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V27-86. 760 records from Arthropoda specimens of Toyama Science Museum. 45 records from Benthic macrofauna abundance of sediment core 13200-004. 33460 records from Records of Invasive Non Native Species held on the Cofnod database. 76 records from BIRDRACE Taubenhaucher. 9016 records from Contribution à la gestion durable des forêts : Caractéristiques écologiques et structurales de la forêt naturelle d’Akpè (Lama) au Sud du Bénin.. 3587 records from Benthic foraminifera of sediment core M25/4-KL13. 11 records from Two new species of the genus Atractoscion, and resurrection of the species Atractoscion atelodus (Günther 1867) (Perciformes: Sciaenidae). 8 records from Flightless Catapionus (Coleoptera: Curculionidae: Entiminae) in Southwest China survive the Holocene trapped on mountaintops: new species, unknown phylogeny and clogging taxonomy. 49 records from Fiocruz/CFP - Coleção de Fungos Patogênicos. 300 records from Collection des données de biodiversité marine de Polynésie française - IRD Nouvelle-Calédonie. 262 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/012-5. 62 records from Kurler Busch (Scharnhorst). 10 records from Description of female of Titidius urucu Esmerio & Lise, 1996 (Araneae: Thomisidae). 397 records from (Appendix A) Planktonic foraminifera abundances in ODP Site 130-807B. 50 records from Occurrence of mammalia relicts at site Buchenloch. 21 records from Sarcodine counts and carbon biomass at station TT011_5-CTD64. 1092 records from Neogene palynomorpha from site 81-555. 571 records from BIRDRACE Havelland. 2 records from On two new synonyms of the orb-weaving spider Orsinome vethi (Hasselt, 1882) (Araneae, Tetragnathidae). 8 records from New species of Raphidascaris (Sprentascaris) (Nematoda: Anisakidae) in Rineloricaria steinbachi (Actinopterygii: Loricariidae) from Northwest Argentina. 100 records from (Figure 5) Distribution of Upper Cretaceous agglutinated benthic foraminifers in ODP Hole 103-640A. 393 records from ENBI-Dataset of GART-GloBIS. 50 records from Antarctic Krill occurrence data from Spanish RV "Fruela". 3 records from A new genus and species of Laelapidae (Acari: Mesostigmata) from Iran. 396 records from Total foraminifera counts of multinet M12/3_MSN558. 2 records from A review of the ant genus Harpegnathos Jerdon, 1851 (Hymenoptera: Formicidae) in the Philippines, with the description of two new species. 18 records from A review of Newportia species in the subgenus Newportides Chamberlin, 1921 (Scolopendromorpha, Scolopocryptopidae, Newportiinae). 8 records from Taxonomy of two endemic Indian skinks, Eutropis bibronii (Gray, 1838) and E. nagarjunensis (Sharma, 1969) (Reptilia: Scincidae), including redescriptions of their types. 498 records from données naturalistes de ALZIAR Gabriel. 35707 records from Herbier Louis-Marie (QFA) - Collection de bryophytes. 23 records from (Table 4) Relative abundance of the major nannofossil groups in the Lower Cretaceous of ODP Hole 113-693A. 5 records from Annelida specimens of Ryukyu University Museum (Fujukan). 50 records from Range table from planktonic foraminifers in ODP Hole 192-1187A. 20 records from A new record of Siler collingwoodi (Araneae: Salticidae) from Japan. 5695 records from Inventario herpetofaunístico del valle semiárido de Tehuacán-Cuicatlán. 2183 records from (Table 8) Distribution of Pleistocene to early Pliocene nannofossils in ODP Hole 108-662A. 201 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-94-GN3619940280200800. 349 records from Total foraminifera counts of multinet POS247/2_MSN1382. 6 records from A new species of fan-throated lizard of the genus Sitana Cuvier, 1829 from coastal Kerala, southern India. 12 records from Monomorium dentatum sp. n., a new ant species from Egypt (Hymenoptera: Formicidae) related to the fossulatum group.. 6 records from Begonia elachista Moonlight & Tebbitt sp. nov., an enigmatic new species and a new section of Begonia (Begoniaceae) from Peru. 367 records from Nekton and plankton counts from Wechselnetz-Hai (300 µm) hauls of cruise GAE 1975/76. 506 records from Mosquitoes (Culicidae) of Ireland. 3070 records from Amphibians and reptiles of Ireland. 1533 records from Recursos hidrobiológicos de la desembocadura del caño Teracay en el río Tomo, Puerto Carreño, Vichada - Proyecto Colombia BIO. 8 records from A new species of the genus Paramesotriton (Caudata: Salamandridae) from Fujian, southeastern China. 6 records from Taxonomy of the Oriental leafhopper genus Favintiga Webb (Hemiptera: Cicadellidae: Deltocephalinae: Drabescini) with description of a new species from China. 47 records from Microplankton abundance at Station MARCH-1998-GN36199804611MNB03 in the euphotic zone of the Aegean Sea in March 1998. Part 1 - diatoms. 34194 records from UF Florida Museum of Natural History Mammals. 24 records from E. E. Green’s collection of scale insects (Hemiptera: Sternorrhyncha: Coccomorpha) in The Natural History Museum, London, U. K.. 14954 records from Inventario florístico y base de datos de la familia Cucurbitaceae en México. 936 records from (Figure 3) Distribution chart of dinoflagellate cysts of Cretaceous age from ODP Hole 103-638B. 16 records from One new species and two redescriptions of Marphysa (Eunicidae, Annelida) species of the Aenea-group from Australia. 3381 records from Poliquetos litorales de la región norte y centro del estado de Veracruz. 57 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB02 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 7 records from A new species of small and highly abbreviated caecilian (Gymnophiona: Indotyphlidae) from the Seychelles island of Praslin, and a recharacterization of Hypogeophis brevis Boulenger, 1911. 30 records from Planktic foraminifera abundance of Hole 17-165. 397305 records from UAM Herbarium (ALA), Vascular Plant Collection (Arctos). 15 records from Occurrence of mammalia relicts at site Victoria Cave. 34 records from Microzooplankton abundance and biomass at station NBP97-08-09-1. 18 records from Description of the Nymph of Tramea binotata (Rambur, 1842) (Odonata: Libellulidae). 758 records from MalaCo, Journal de Malacologie continentale [2005-]. 177 records from (Fig. 2) Abundance of Uvigerina pygmaea in sediment core MD95-2040. 12394 records from Platynotina (Coleoptera: Tenebrionidae) collections on the World. 32 records from The Stenus cirrus group (Coleoptera, Staphylinidae) in Fujian, East China. 1008 records from (Table S1) Relative abundances of coccolithophore taxa in surface sediment samples from the Equatorial and Southeastern Pacific. 90 records from Seven new species of Loneura Navás (Insecta: Psocodea: ‘ Psocoptera’: Ptiloneuridae) from Valle del Cauca, Colombia. 42979 records from The census of national forest of Benin .. 154 records from Planktic foraminifera abundance of Hole 84-569A. 95918 records from Mammals Specimens. 2 records from Two new species of the genus Metaxonchium Coomans & Nair, 1975 (Nematoda, Dorylaimida, Belondiridae) from Vietnam. 58 records from Birkenpilz. 248 records from Birds of Grand Kru Liberia. 1 records from First record of spongillaflies (Neuroptera: Sisyridae) from Colombia. 54 records from Données naturalistes de Philippe VEILLON. 97 records from Nematode densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 106 records from Weidegut Rechab. 3408 records from CSIRO, Jack Mackerel surveys, 1978. 19628 records from National System of Protected Areas in Poland - Plants. 107 records from Dichomeris Hübner, 1818 (Lepidoptera, Gelechiidae, Dichomeridinae) from Cambodia, including associated Chinese species. 149 records from Occurrence of mammalia relicts at site Erdhöhle. 2677 records from Bryophyte diversity in grassland. 897 records from Trichoptera of the UNESCO biosphere reserve of the Palatinate forest / North Vosges (Germany, France). 986 records from (Figure 3) Distribution of Upper Cretaceous agglutinated benthic foraminifers in ODP Hole 103-641A. 32 records from Observations issues des suivis Argos des phoques gris en Atlantique et Manche Mer du Nord. 15 records from City of Edinburgh Natural Heritage Service - Bonaly Moorland Moth Survey. 51 records from Tití Gris (Saguinus leucopus) en remanentes de bosque de los departamentos de Caldas y Antioquia. 48 records from Paraorosius, a new genus of leafhopper (Hemiptera: Cicadellidae: Deltocephalinae: Opsiini), with description of a new species from the Middle East. 24 records from Perlesta armitagei n. sp. (Plecoptera: Perlidae): More cryptic diversity in darkly pigmented Perlesta from the eastern Nearctic. 2614 records from Phytoplankton abundance in surface water in October 1997, Chimbote, Peru. 94372 records from New Zealand Biodiversity Recording Network. 6 records from A new species of the genus Colilodion Besuchet, 1991 (Coleoptera: Staphylinidae: Pselaphinae) from Mindanao, the Philippines. 2 records from Données naturalistes de CARON Nicolas. 12 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Donacobiidae. 6 records from Description of the mature larva of Austrolimnius nyctelioides (Germain, 1892) and A. elatus Hinton, 1941 (Coleoptera: Elmidae). 2 records from The tenth member of stout newt (Amphibia: Salamandridae: Pachytriton): Description of a new species from Guangdong, southern China. 2603 records from Museu Paraense Emílio Goeldi - Paleoinvertebrate Collection. 5 records from Redescription of a little-known spider species, Mesiotelus lubricus (Simon, 1880) (Aranei: Liocranidae) from China. 7075 records from SMNS Herpetologie. 20 records from Dinoflagellate abundance of Hole 81-552. 14 records from (Table 4b) Abundances of Globorotalia menardii in sediment core INMD-111BX. 8 records from A new species of Ergasilus von Nordmann, 1832 (Copepoda: Cyclopoida) from the gills of a dasyatid ray, Himantura oxyrhyncha (Sauvage, 1878) from West Kalimantan, Indonesia. 186 records from The jumping plant-lice of the Neotropical genus Tainarys (Hemiptera: Psylloidea) associated with Anacardiaceae. 63 records from Table 1. Location, water depth, grain size distribution, organic carbon and carbonate contents of the investigated Arctic and Antarctic surface sediment samples. 1445 records from Pollen analysis of sediment profile SI0 from Siethener See. 2068 records from Colección Zoológica de la Universidad del Tolima (CZUT)-Anfibios. 355 records from Total foraminifera counts of multinet POS231/3_MSN1329. 33 records from Microplankton counts and carbon biomass at station TT008_5-CTD18. 1002 records from Herbario HUAZ Enrique Forero. 12 records from Coendutermes tucum Fontes (Isoptera, Termitidae, Nasutitermitinae): description of the imago caste and additional notes. 1399 records from North Atlantic (Rockall Plateau) coccolith assemblage data for MIS 5 of ODP Hole 162-980B. 128 records from Kabelskebach (Kabelsketal, Saalkreis). 4 records from Four new generic and 14 new specific synonymies in Pholcidae, and transfer of Pholcoides Roewer to Filistatidae (Araneae). 114 records from Pollen analysis of sediment core GeoB1007-4. 1336 records from Freshwater Macrophyte Survey Data. 286 records from Naturalis Biodiversity Center (NL) - Orthopteroidea. 270 records from Plasm bearing foraminifera counts of multinet M21/2_MSN639. 904 records from Gelände des IVL (Zeckern). 2414 records from Planktic foraminifera abundance of Hole 72-516A. 96 records from Fauna herpetológica de los Parques Ecológicos Distritales Humedales Bogotá, D.C.. 1821763 records from Hawk Migration Association of North America - HawkCount. 226079 records from E. C. Smith Herbarium (ACAD). 32 records from Foraminifera abundance of Hole 60-453. 24 records from Planktic foraminifera abundance of Hole 42-372. 80 records from Museu Paraense Emílio Goeldi - Platyhelminthes Collection. 1711844 records from EBCC Atlas of European Breeding Birds. 852 records from Estructura poblacional, variación genética y conservación de tres especies del género Pinus, endémicas de México. 316 records from Base de datos de Rana catesbeiana.. 10 records from Taxonomic revision of Saffron-billed Sparrow Arremon flavirostris Swainson, 1838 (Aves: Passerellidae) with comments on its holotype and type locality. 1992 records from Phytoplankton abundance in surface water in July-August 1996, Pisco, Peru. 124 records from Uroptychus nitidus (A. Milne-Edwards, 1880) and related species (Crustacea: Decapoda: Anomura: Chirostylidae) from the western Atlantic. 3700 records from Données diverses du PnrL. 7319 records from Consolidación y sistematización de las colecciones de referencia de peces y mamíferos marinos del ITESM Campus Guaymas. 78 records from Occurrence of mammalia relicts at site Fuchsloch im Krockstein. 4726 records from Avifauna en un área perturbada del bosque andino en el Parque Nacional Natural Farallones de Cali, corregimiento de Pance, Valle del Cauca (Colombia). 96 records from SYMBIOSE_2017_12_18. 953 records from Caracterización del hábitat y patrones de distribución del gorrión serrano (Xenospiza baileyi) en el sur del Valle de México. 222 records from The bees (Hymenoptera: Apoidea) of the Maltese Islands. 99 records from (Table 3) Abundance of benthic foraminifera and ostracoda in bottom sediments from the Ashadze-1 Hydrothermal Field. 9530 records from (Table 10A) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-588. 1821 records from Inventario florístico de la Sierra de San Carlos, Tamaulipas. 192 records from Occurrence of mammalia relicts at site Vindija. 20 records from Description of the larval stages of the Shield Darter, Percina peltata (Pisces: Percidae), in New York.. 1112644 records from Museums Victoria provider for OZCAM. 40374 records from Alterra (NL) - Entomofauna inventory in riverside grasslands. 375 records from Total foraminifera counts of multinet M21/2_MSN647. 943 records from Herbivorie_Pflanzenebene_2008. 223114 records from SysTax - Zoological Collections. 4 records from A new amphibious troglobitic styloniscid from Brazil (Isopoda, Oniscidea, Synocheta). 27 records from Epimeria cleo sp. nov., a new crested amphipod from the Ross Sea, Antarctica, with notes on its phylogenetic affinities (Crustacea, Amphipoda, Eusiroidea, Epimeriidae). 1 records from A new species of nurse-frog (Aromobatidae, Allobates) from the Madeira River basin with a small geographic range. 348 records from Updated list of bumblebees (Hymenoptera: Apidae) from the Spanish Pyrenees with notes on their decline and conservation status. 1016413 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 22 records from Pteroceraphron Dessart new to the USA (Hymenoptera: Ceraphronoidea). 3724 records from corrego_fazendinha-gallery-forest_v2. 561 records from UWIZM Mammals. 2845 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 39852479 records from INPN - Données flore des CBN agrégées par la FCBN. 1661 records from Arácnidos de Centroamérica. 9 records from Oxynoemacheilus kentritensis, a new species from the upper Tigris drainage in Turkey with remarks on O. frenatus (Teleostei: Nemacheilidae). 32 records from A new species of Mesovelia (Heteroptera: Gerromorpha: Mesoveliidae) from South America, with identification key and notes on Colombian species. 48 records from Meiofauna abundance in sediment core 12930-036. 270 records from (Table 4) Benthic foraminifera genera assemblage at DSDP Section 80-548A-11-3. 3298 records from Benthic foraminifera abundance of Hole 47-397. 4960 records from Diversidad y conservación de orquídeas de la región de Chimalapa, Oaxaca, México. 74 records from Abundance of benthos infauna at station GIK23043-2. 450 records from Data from ILAM surveys conducted by ARCOS in Mukura landscape for year 2016. 286 records from (Figure 2) Distribution chart of dinoflagellate cysts of Cretaceous age from ODP Hole 103-638C. 18 records from Fossil occurrence of planktonic foraminifera from IODP Hole 315-C0001I. 70 records from Three new species of Mesovelia Mulsant & Rey (Hemiptera: Heteroptera: Mesoveliidae) from India. 2128 records from Freshwater Pest Plants. 545304 records from Florida Keys Reef Visual Census 2007. 2617 records from (Table 3) Occurrences of planktonic foraminifers in samples from ODP Hole 105-647A. 16 records from Macropsini (Hemiptera: Cicadellidae) of Thailand, with description of two new species and three new country records. 13434 records from LSUMZ Mammal Tissues. 240416 records from Inventaire National du Patrimoine Naturel : Poissons d'eau douce de France. 568 records from Banco de Germoplasma Vegetal del Jardín Botánico de Olarizu (Vitoria-Gasteiz)/Olarizuko Lorategi Botanikoaren Landare Germoplasma Bankua (Vitoria-Gasteiz). 8 records from Cliona acephala (Porifera: Demospongiae: Clionaida), a new encrusting excavating reef sponge from the Colombian Caribbean belonging to the Cliona viridis species complex. 477 records from Nannofossil abundance of Hole 94-611D. 14 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 27130 records from Herbario de Universidad de Murcia: MUB. 488 records from Pollen profile from sediment core AV14_K2-1. 564 records from Revisión de las Agavaceae (sensu stricto), Crassulaceae y Liliaceae incluidas en el PROY-NOM-059-ECOL-2000. 90 records from Coccolith counts of multinet M32/5_MSN977. 3 records from A new species of Pasiphaea Savigny, 1816 (Crustacea, Decapoda, Pasiphaeidae) from the southwestern Atlantic. 111 records from Checklist of decapods (Crustacea) from the coast of the São Paulo state (Brazil) supported by integrative molecular and morphological data: I. Infraorder Caridea: families Hippolytidae, Lysmatidae, Ogyrididae, Processidae and Thoridae. 164 records from DREAL_PACA_-_N2000_-_Ville_de_Fréjus_2017_12_18. 3720 records from Sponge collection of National Museum of Nature and Science. 40 records from Two new species of Curculionichthys (Siluriformes: Loricariidae) from the rio Amazonas basin, Brazil. 15276 records from Crustaceos del Museo de Ciencias naturales de la Universidad Simón Bolívar. 578 records from (Table 2) Sea surface temperature reconstruction from sediment core MD88-770. 2 records from A new species of Tapiena (Orthoptera: Tettigonioidea: Phaneropterinae) from Brunei Darussalam (Borneo, Southeast Asia). 111078 records from Seasearch Marine Surveys in Ireland. 70 records from Urwald 3 (Bad Waldsee). 393 records from (Table 7) Ostracod assemblages of sediment core 9408. 1266 records from (Appendix A2) Relative abundances of benthic foraminifera and stable carbon isotope ratios of Nuttallides truempyi at the Paleocene-Eocene thermal maximum in ODP Hole 198-1210B in the central Pacific. 1208 records from (Table 2) Relative abundance of planktic foraminifera in Maastrichtian sediments of DSDP Hole 3-21 from the Rio Grande Rise, South Atlantic Ocean. 2029 records from Biodiversidad asociada a mantos de rodolitos y praderas de pastos marinos en Bahía Concepción, BCS. 7617 records from Range table from planktonic foraminifers in ODP Hole 139-857A. 22186 records from Abundances indices and biological traits of juvenile salmon sampled in the Oir river (France). 26 records from First record of Africactenus Hyatt, 1954 and redescriptions of two poorly known species of Ctenus Walckenaer, 1805 (Araneae, Ctenidae, Cteninae) from India. 2 records from Parasitism of Hymenoepimecis manauara Pádua & Oliveira (Hymenoptera: Ichneumonidae: Pimplinae) on Leucauge henryi Mello-Leitão (Araneae: Tetragnathidae) in Brazilian Amazonian. 134 records from Review of Lecithoceridae (Lepidoptera: Gelechioidea) in the Oceanian Region, with description of a new species and a checklist of the family. 99 records from (Table 5) Vertical distribution of live benthic foraminifera in surface sediments at Bouvet Island stations. 192 records from Total foraminifera counts of multinet M42/3_MSN1369. 3 records from The current status of Neocnus Arredondo, 1961 (Mammalia: Edentata: Pilosa: Megalonichidae) and a replacement name for its junior homonym in the sea cucumber family Cucumariidae (Echinodermata: Holothuroidea: Dendrochirotida: Cucumariidae). 12 records from Zanna robusticephalica sp. nov. (Hemiptera: Fulgoromorpha: Fulgoridae) from China, with comments on some ultrastructural characters of the new species. 2 records from Two new species of Dactylonotus Parent, 1934 (Diptera: Dolichopodidae) from South Africa and a key to Afrotropical species. 1855 records from TWIC Hedgehog Public Survey. 8 records from A new carpenter ant, Camponotus parabarbatus (Hymenoptera: Formicidae) from India. 538 records from Range table from planktonic foraminifers in ODP Hole 155-934A. 745 records from Sediment components of core SO82-4. 10 records from One new Pseudopoda species group (Araneae: Sparassidae) from Yunnan Province, China, with description of three new species. 89 records from Distribution of planktonic foraminifera of sediment core SH1972_13. 566 records from Total foraminifera counts of multinet M6/7_MSN116. 388 records from Lindau im Bodensee. 337105 records from Herbarium Willing. 70 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Rhinocryptidae. 4227 records from Hongos ectomicorrizógenos y myxomycetes asociados con Picea chihuahuana en la Sierra Tarahumara. 3432 records from KTU Pinophyta. 80 records from Données de Rhône-Alpes transmises par Pascal Peyrache.. 4 records from A new species of Selatosomus Stephens and the occurrence of Pristilophus melancholicus (Fabricius) in China (Coleoptera: Elateridae: Dendrometrinae). 844 records from Crustacés Branchiopodes Phyllopodes de France. 1588 records from (Table T2) Calcareous nannofossil abundance of ODP Hole 171B-1052A sediments. 10 records from Fledermäuse u. nachtaktive Insekten. 15442 records from Chondrichthyans Of Ireland. 56 records from Admiralty Bay Benthos Diversity Data Base (ABBED). Pycnogonida.. 718 records from Inventaire malacologique du site Natura 2000 FR9301537 de la Montagne de Lure (2002, ONF/MNHN). 20027 records from Coleção de Porifera do Museu Nacional - UFRJ. 279 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto1-10. 1308 records from Planktic foraminifera counts of sediment core V25-59. 93 records from (Table 3) Oxygen and carbon isotope ratios of Globigerinoides sacculifer of ODP Hole 134-828A. 7848 records from Insect specimens of Toyota City Nature Sanctuary. 1642 records from Sudeniederung (Amt Neuhaus). 4636 records from DREAL_PACA_-_N2000_-_Syndicat_Mixte_d'Aménagement_de_la_Vallée_de_la_Durance_2017_12_18. 175564 records from Bryophyte data for Great Britain and Ireland from the British Bryological Society held by BRC: data compiled post-Atlas. 666 records from O Tu Wharekai algae survey. 392 records from Range table from benthic foraminifers in ODP Hole 171-1052E. 12 records from Taxonomy and biology of Simulium clarkei Stone & Snoddy (Diptera: Simuliidae), a poorly known black fly of the southeastern United States. 96 records from Planktic foraminifera abundance of Hole 47-397. 124 records from North Marine Region whaler shark collection records (DEW collation), Australia (1999- 2005). 1140 records from Flora ficológica marina de Tamaulipas. 71 records from Abundance and carbon biomass of phytoplankton at station TT012_5-CTD13. 543 records from Stable isotope analysis on sediment core PS2644-2. 2474 records from (Appendix B) Distribution of planktonic foraminifera at DSDP Hole 72-518. 114012 records from Vascular plants collection of Hiratsuka City Museum. 23440 records from Colección Viva del Jardín Botánico de Bogotá. 2902 records from Plantas de la transición Andino-Amazónica del departamento del Caquetá - Proyecto Colombia BIO. 248 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 60 records from VFD-H.: Rheingau: Bärstadt. 69 records from Eudraces barclayi sp. nov., with some notes on the genus Eudraces Marshall (Coleoptera: Curculionidae: Entiminae: Myorhinini). 318 records from Inventario de invertebrados marinos del SFF Isla Malpelo, Proyecto Colombia BIO. 460 records from (Table 11) Distribution of coccoliths along Core AMK7-786 from the Tajura Rift. 150 records from Streuobstwiese Stedar. 16 records from Two new species of Scymnini (Coleoptera: Coccinellidae) from Karnataka, India. 64 records from Bacteria Collection of the Seto Marine Biological Laboratory, Kyoto University. 7 records from Microplankton counts and carbon biomass at station TT007_12-CTD145. 910 records from Relativ abundances of dead fauna of benthic foraminifera in surface sediments (Table C2.2). 28 records from Nano and microzooplankton abundance and biomass at station NBP97-01-20-3. 63 records from Microzooplankton abundance and biomass at station TT043_29-1. 15 records from Morphology and infraciliature of two new earthworm ciliates, Hoplitophrya polymorphus sp. nov. and Anoplophrya simplex sp. nov. (Ciliophora: Oligohymenophorea: Astomatia). 78 records from Etnomicología en la Sierra de Santa Marta, Veracruz. 405 records from Pollen profile from Achenhang. 2421 records from Planktic foraminifera distribution of sediment core 75KS52. 8 records from A new species of Auriculostoma (Trematoda: Allocreadiidae) from the intestine of Brycon guatemalensis (Characiformes: Bryconidae) from the Usumacinta River Basin, Mexico, based on morphology and 28 S rDNA sequences, with a key to species of the genus. 732 records from Distribution of living benthic foraminifera in sediment cores of cruise M77 Leg 1 and 2, 63-2000 µm fraction. 46 records from Range table from planktonic foraminifers in ODP Hole 180-1110A. 1172 records from EPOS3: SeaStars (Echinodermata, Asteroidea). 5701 records from Gillnet test fishing and radiocaesium (Cs-137) of brown trout (Salmo trutta) and Arctic char (Salvelinus aplinus) 2008 and 2009 from 20 Central Scandinavian lakes: Occurrences. 346 records from Foraminifera species abundances from tow TT011_11-MOC72. 566 records from HSU Vertebrate Museum Birds Collection. 56 records from New species of ant-mimicking jumping spiders of the genus Myrmarachne MacLeay, 1839 (Araneae: Salticidae) from north Queensland, Australia. 24 records from Kinderwald Hannover. 105 records from Phytoplankton abundance at station Rigel_5_2005-04 in April 2005, Chipana, Chile. 29004 records from Lepidoptera (Rhopalocera y Heterocera) de áreas prioritarias para la conservación en la Península de Yucatán, con registros de adultos y estados inmaduros. 2200 records from Foraminifera abundance of Hole 64-478. 656 records from Unser Schulgelände. 19280 records from Carabidae of Poland. 92 records from Nannofossil abundance of Hole 3-21A. 6 records from Planktic foraminifera abundance of Hole 54-419. 284 records from Birdrace-Alte_Socken-Cuxhaven. 89102 records from MEXU/Plantas Vasculares. 9877 records from Derbyshire Invasive Non-Native Species (INNS) 1900 - 2014. 10490 records from Inventario de macroalgas de Bahía de Banderas: Fase I y Fase II. 15878 records from Botany registration database by Danish botanists. 3 records from A remarkable new species of the genus Lepisiota Santschi (Hymenoptera: Formicidae) from Oman and the United Arab Emirates with a key to the Arabian species. 550 records from Colecciones Zoológicas de la Universidad de León, Colección de Gasterópodos. 15 records from Three new species of Entomobrya from Poland (Collembola, Entomobryidae). 24 records from Ohemoor (Hamburg/Norderstedt). 98 records from Phytoplankton abundance at station Rigel_4_2005-02 in Febraury 2005, Chipana, Chile. 146 records from Benthic foraminifera abundance of Hole 80-550. 80 records from Additions to the knowledge of the land snails of Sabah (Malaysia, Borneo), including 48 new species. 4 records from First description of the last instar larva and pupa of the aquatic crane fly Limnorimarga limonioides (Alexander, 1945) (Diptera: Limoniidae). 68492 records from Collection Ichthyologie - SNSD. 2500 records from National Museum Of Marine Science & Technology. 169 records from Occurrence of mammalia relicts at site l´Abri de Rhodes II. 870 records from Seasearch Pink Sea Fan, Eunicella verrucosa, Survey. 6722 records from Actualización de la base de datos del Herbario de la Universidad de Sonora (USON). 6 records from First record of the genus Soliperla (Plecoptera: Peltoperlidae) from China with description of a new species. 6 records from Taxonomy and Natural History of Strumigenys thaxteri Wheeler and Strumigenys reticeps (Kempf) (Hymenoptera: Formicidae). 1712 records from Nannofossil abundance of Hole 29-279A. 228 records from Chough sightings data, Northern Ireland, 2007-2010. 1321 records from Vom Gipfel ins Moor, Transekt im NSG Allgäuer Hochalpen. 756 records from (Appendix A) Benthic foraminiferal abundances and principal component scores in middle to late Pliocene desiments of DSDP Hole 94-607 from the North Atlantic. 125918 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Herpetology National Collection (MACNHe). 6039 records from Plantas de La Frontera (ecorregión 12.1.1.1), e inventario florístico del Rancho El Aribabi, municipio de Imuris, Sonora. 3216 records from Phytoplankton abundance in surface water in February 1998, Ilo, Peru. 163 records from Lochaber wild boar/feral pig camera trap survey, 2015. 2810 records from Fonoteca Zoológica, Museo Nacional de Ciencias Naturales, Madrid: FZ_AVES. 11503 records from Fungi collection of Jyväskylä University Museum. 2374 records from Florística y biogeografía de algunos bosques mesófilos de la Huasteca Hidalguense: Fase II (Tlahuelompa y Eloxochitlán). 191 records from (Table 1) Constituents of the sand-size fraction of ODP Hole 139-856A. 8 records from A new canopy-dwelling species of Dendrelaphis (Serpentes: Colubridae) from Sinharaja, World Heritage Site, Sri Lanka. 1312316 records from NMNH Paleobiology Specimen Records. 98963 records from DMNS Bird Collection (Arctos). 140 records from Abundance of coccosphere-units of sediment core GIK23071-2. 42570 records from Bird Collection of Museum and Institute of Zoology PAS. 268 records from Birdrace-Team_Havelland-Havelland. 9126 records from Sizing Ocean Giants. 942 records from Invertebrate collection of the Seto Marine Biological Laboratory, Kyoto University. 6060 records from Free-living Nematodes from Patagonia coastal lagoons (Chubut, Santa Cruz, Argentina).. 1 records from Lissotes working-group. 58 records from Planktic foraminifera abundance of Hole 84-567. 331 records from Die Teiche im Britzer Garten. 6 records from Two new species of the genus Gibbotettix Zheng, 1992 (Orthoptera: Tetrigidae, Cladonotinae) from China. 28 records from Laophontodes typicus T. Scott (Copepoda, Harpacticoida, Laophontodinae) - discovering a species complex by morphology. 530 records from AIS Wildtype Populations of Arabidopsis. 278 records from (Appendix Table 3) Distribution of live benthic foraminifera in surface sediments. 910 records from Bearded Tit National Survey in Britain 2002. 20 records from Two new butterfly species (Lepidoptera: Rhopalocera) from Mount Cameroon, Gulf of Guinea Highlands, Cameroon. 62000 records from Elephant Seal Sightings, Macquarie Island. 12 records from Review of the genus Metopheltes Uchida, 1932 (Hymenoptera, Ichneumonidae) with description of a new species from Vietnam. 2 records from On the Chilopoda from Turkey. 8 records from A new species of the remarkable brittle star genus Astrophiura (Echinodermata: Ophiuroidea) from the western Atlantic Ocean. 10 records from Description of a new Gibbaranea (Araneae: Araneidae) from the Western Mediterranean. 31 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-14. 2706 records from Percentages of planktonic foraminifera species in sediment core RC24-7. 1387 records from Estudio de la diversidad florística de la región de Nizanda en el Istmo de Tehuantepec, Oaxaca. 1350559 records from Herbarium specimens of Université de Montpellier 2, Institut de Botanique (MPU)). 813 records from Ville de Trois-Rivières - Bioblitz 2012. 12 records from A new species of Stasimopus from the Eastern Cape Province of South Africa (Araneae, Mygalomorphae, Ctenizidae), with notes on its natural history. 128 records from Chenopodium vulvaria. 1274 records from Inventaire de l'îlot du Lédénez Vraz. 59 records from Phytoplankton abundance at station Sechin_2003-11-06_2, Casma, Peru. 193 records from Succession of benthic hard-bottom communities abundance at station Errina2012_AG. 189 records from BIRDRACE Brut. 2 records from Description of a new species of the genus Mongolotettix Rehn, 1928 (Orthoptera: Acrididae) from Fujian, China. 3 records from Occurrence of mammalia relicts at site Egtved. 150 records from Estudio de la variabilidad genética de Fundulus lima y sus relaciones filogeográficas con otros fundúlidos (Pisces: Fundulidae) de la Península de Baja California, México. 1694 records from PAMP-tracheo: Vascular plants in La Demanda and Cameros mountain ranges (La Rioja, Spain). PhD project, L.M. Medrano. 144 records from Birdrace-Buteo2DO-Dortmund. 13142 records from Mammalia fossil Kleinsäuger - SMF. 135 records from Total foraminifera counts of multinet M21/4_MSN719. 3408 records from DREAL Auvergne - Insectes - 2015. 2514 records from (Table A.01) Planktic foraminiferal census data of sediment core GIK23414-7. 141 records from Planktic foraminifera assemblage in sediment core GIK23066-2. 324 records from Antarctic fish Gobionotothen gibberifrons. 102 records from University of Amsterdam (NL) - Páramo Vegetation Research, Bordoncillo - Nariño, Colombia. 114 records from Range table from planktonic foraminifers in ODP Hole 169-1038I. 548 records from Herpetological Collection at the Wildlife Institute of India Vertebrate Museum. 7 records from Vietelmis jablonskii, a new species of riffle beetle from Laos and Thailand and new faunistic records on Vietelmis Delève, 1968 from Malaysia (Coleoptera: Elmidae). 8 records from A new black fly species of Simulium (Simulium) (Diptera: Simuliidae) from Taiwan. 681 records from Pöhlberg bei Annaberg. 21 records from Plasm bearing foraminifera counts of multinet POS231/3_MSN1336. 95 records from "Wildnis erleben" - "Vielfalt erlebbar machen" - Botanischer Garten u.Chrimmitschauer Wald. 208 records from Birdrace-RMD_Die_Gipfelstürmer-Main-Taunus-Kreis. 10 records from Microzooplankton abundance and biomass at station TT050_11-4. 1698 records from Collection Paleoanthropology SMF. 715 records from Total foraminifera counts from multinet M32/5_MSN976. 4000 records from Mollusk Collection of Yokosuka City Museum. 373 records from Dinocyst occurrences and zonations from IODP Hole 313-M0029A. 4642 records from Dataset of fungus gnats (Diptera,Sciaroidea) from Møre og Romsdal county in Norway. 936 records from Planktic foraminifera abundance of Hole 22-214. 2073 records from (Table 6) Planktonic foraminifera in ODP Holes 139-856A and 139-857A. 28 records from Nano and microzooplankton abundance and biomass at station NBP97-01-14-2. 16012 records from Knerer collection / Gschwendtner property. 18542 records from DBG Sam Mitchel Herbarium of Fungi. 2060 records from Benthic foraminifera and algae abundance of Hole 81-555. 8684 records from (Appendix C) Stratigraphic range and relative abundance of Neogene planktonic foraminifer taxa in ODP Hole 120-751A. 2 records from Description of a new neotropical species of Xiqilliba Kramer (Hemiptera: Cicadellidae: Neocoelidiinae). 2416 records from Ecology, structure and dynamics of private plantations of Teck (Tectona grandis Lf) of the Department of the Atlantic (South Benin), 2011. 2272 records from (Table 1) Distribution of agglutinated benthic foraminifera in lower Cretaceous sediments of DSDP Hole 27-263 in the Cuvier Abysaal Plaine, Indian Ocean. 4 records from Ceraphron krogmanni (Hymenoptera: Ceraphronidae), a new species from Lower Saxony with unusual male genitalia. 6 records from New data on the taxonomy, ecology, and conservation of the rediscovered Louisea edeaensis (Bott, 1969) (Brachyura: Potamoidea: Potamonautidae), an endangered freshwater crab from Cameroon. 2421 records from Census of plant species in Toffo forest reserve. 60165 records from CMC Cincinnati Museum Center Invertebrate Paleontology. 3349 records from Satellite tracking of female olive ridley sea turtles (Lepidochelys olivacea) nesting in the Wessel Islands, Northern Territory, 2005. 108 records from Elgin Road 3 year observations. 31 records from Analyses of the recent components of sediment core PS1422-1. 190 records from Abundanz_Infloreszenzenschlupf_Pflanzenebene_2008. 249 records from RHS Fuchsia Gall Mite (Aculops fuchsiae) monitoring. 827 records from Schatzinsel Norderney. 78380 records from Freshwater fishes of Poland. 4 records from The polyps of Oceania armata identified by DNA barcoding (Cnidaria, Hydrozoa). 111 records from Phytoplankton abundance at station Rigel_3_2005-04 in April 2005, Chipana, Chile. 12 records from On Starengovia Snegovaya, a genus of Asian nemastomatines (Arachnida: Opiliones: Nemastomatidae). 2 records from Myriopoden von Epirus. 2 records from A new genus and species of Ingolfiellidae (Crustacea, Ingolfiellida) from the hyporheic zone in the Sierra de la Ventana, and its biogeographic relevance. 1648 records from Données naturalistes de Philippe RAVAT. 59 records from Occurrence of recent nannoplankton in surface sediments at M1_MULT243, Arabian Sea (Fig. 2). 30920 records from MVZ Egg and Nest Collection (Arctos). 1836 records from Fossil (GNHM-FO). 3304356 records from CSIC-Real Jardín Botánico-Anthos. Sistema de Información de las Plantas de España. 6 records from A new species and key to all known species of the genus Filchnerella Karny, 1908 from China (Orthoptera: Acridoidea, Pamphagidae). 6 records from Australian Formicidae.. 1163 records from Coccolith abundence from sediment core GeoB1028-5. 22 records from ENS inventaires. 99998 records from observe_tuna_bycatch_ecoscope. 7880 records from Natural England bat roost visit records from 2013 onwards. 21 records from New species of Narberdia Burke from México and Central America (Coleoptera: Curculionidae). 1094 records from RMT Trawl catch from the 2005/06 V3 BROKE-West voyage - Fish. 277 records from (Table 6) Planktonic foraminifer species distribution, abundance, and preservation in DSDP Site 92-601. 17128 records from Bird specimens of Himeji City Science Museum. 548767 records from Naturalis Biodiversity Center (NL) - Aves. 354 records from (Appendix) Ostracodes at DSDP Leg 72 Holes. 150 records from Range table from planktonic foraminifers in ODP Hole 182-1131B. 42 records from Hungarosoma bokori Verhoeff, 1928 (Diplopoda: Chordeumatida): new insights into its taxonomy, systematics, molecular genetics, biogeography and ecology. 3 records from Dispatch from the field II: the mystery of the red and blue Opadometa male (Araneae, Tetragnathidae, Opadometa sarawakensis). 31 records from A review of Labidostomis species similar to L. longimana from southeastern Europe with descriptions of two new species from Greece and Turkey (Coleoptera: Chrysomelidae: Cryptocephalinae: Clytrini). 4634 records from University of Manitoba (WIN) - Lichen Collection. 8142 records from CSIC-Real Jardín Botánico-Colección de Hepáticas (MA-Hepat). 2 records from A new genus and species of bark mantis from Thailand, with an updated key to the bark mantis genera of the Oriental region (Insecta: Mantodea). 2 records from A new species of Enoplomischus from Kenya (Araneae: Salticidae: Leptorchestinae). 568 records from Localities for the arachnid genus Acuclavella (Opiliones, Ceratolasmatidae). 382 records from Planktic foraminifera abundance of Hole 67-499. 1890 records from Inventario de Aves Mámbita. 180 records from Down-core abundances of Turborotalia quinqueloba and Globorotalia inflata of sediment core GeoB5546-2. 584 records from Gymnotus ucamara: a new species of Neotropical electric fish from the Peruvian Amazon (Ostariophysi: Gymnotidae), with notes on ecology and electric organ discharges.. 1002 records from Recent noteworthy findings of fungus gnats from Finland and northwestern Russia (Diptera: Ditomyiidae, Keroplatidae, Bolitophilidae and Mycetophilidae). 10 records from First record of Pulvinaria urbicola Cockerell (Hemiptera: Coccidae) from India, with a key to the Indian species of Pulvinaria Targioni Tozzetti. 1540 records from (Appendix A) Relative abundance of planktonic foraminifera in ODP Hole 117-723A. 10 records from A new burrowing crayfish of the genus Fallicambarus Hobbs, 1969 (Decapoda: Cambaridae) from the Red River Drainage of the southcentral United States. 91356 records from Données naturalistes de Damien AVRIL. 250 records from Schulhof der Astrid-Lindgren-Schule Elmshorn. 4 records from Replacement names for two homonyms of Liothrips brevitubus Karny: one from California, the other for a species damaging Jatropha crops in Mexico. 15823 records from Naturalis Biodiversity Center (NL) - Echinodermata. 331 records from Size of planktic foraminifera at CTD station PS55/082-1. 48 records from Liether Park 2 (LMS), Klasse 6c. 806 records from Revision of Afrotropical Dyscritobaeus Perkins, 1910 (Hymenoptera: Scelionidae). 39700 records from Universitat de València, Colecciones de Criptógamas: VAL_Lich. 4 records from A new species of the genus Ancylocheles Haig, 1978 (Crustacea: Decapoda: Anomura: Porcellanidae) from Gujarat, northwestern India. 154 records from BIRDRACE Die Borner. 32 records from Microplankton abundance at bottle station SEPT-1999-K6. 26 records from Seven new species of the genus Xestoleberis (Ostracoda: Podocopida: Cytheroidea) from the Fiji Archipelago. 401 records from Noble Chafer: Post-BAP records from 1998 onwards. 12629 records from (Table T6) Foraminifer distribution in ODP Hole 188-1167A sediments. 698 records from RISC Non-Native Species Records for Muntjac. 1982 records from Foraminifera abundance of Hole 64-481A. 1089 records from The cicadas (Hemiptera: Cicadidae) of India, Bangladesh, Bhutan, Myanmar, Nepal and Sri Lanka: an annotated provisional catalogue, regional checklist and bibliography. 2034 records from Planktic foraminifera abundance of Hole 26-253. 8 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-962D. 78 records from Natura 2000 Complexe de l'étang de Lindre, forêt de Romersberg et zones voisines. 2088 records from Publicación de la obra: American species of Acacia (Leguminosae; Mimosoideae). 189342 records from Wikiplantbase #Toscana. 1580 records from Range table from ostracoda in ODP Hole 143-865B. 2972 records from Mammal collection NTNU University Museum. 22768 records from Records of the Queensland Plant Pathology Herbarium. 993 records from Amphibia collection of the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 188 records from Birdrace-Erlanger_Piepmätzchen-Erlangen/Höchstadt. 392 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB07 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates. 16746 records from Polish seed gene bank – historical passport data of accessions. 256 records from Westerwälder Umwelt- und Naturschutztag an der Fuchskaute im Westerwald. 1320 records from (Table 8D) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 89-586B, Sections 15-4 through 19-3. 6 records from A new species of Misetus Wesmael, 1845 (Hymenoptera, Ichneumonidae, Ichneumoninae, Phaeogenini) from Italy, with updated key to the females of Palaearctic species. 3039 records from Plant (NHMC-PL). 36000 records from Colección Herpetológica "Lic. Blanca Beatriz Alvarez" - Facultad de Ciencias Exactas y Naturales y Agrimensura - Universidad Nacional del Nordeste. 62 records from Herbier Husnot, Hepatica Galliae. 4 records from Hildener Heide - Spörkelnbruch (Haan). 25 records from Descriptions, transference and new records of Lamiinae from Central and South America (Coleoptera, Cerambycidae). 3877 records from Peces y Mamíferos de la región de Norogachi, Alta Sierra Tarahumara, Chihuahua. 4151 records from Patrones de variación espacial y temporal de la biodiversidad fitoplanctónica de los cenotes abiertos de Yucatán. 83826 records from University of British Columbia - Spencer Entomological Collection (UBCZ). 11 records from New Black Fungus Gnats (Diptera, Sciaridae) of North America. Part IV. Genera Eugnoriste Coquillett and Keilbachia Mohrig. 720 records from Küstenschutzwald. 16670 records from The Diatom Collection of Franz Josef Weinzierl at the Botanische Staatssammlung München. 50702 records from Herbário da Pontifícia Universidade Católica do Paraná - HUCP. 17 records from Inventarios de Herpetos de la Microcuenca de la Quebrada Agua Blanca, Vereda Marroquín, Yopal, Casanare. 90 records from Range table from benthic foraminifers in ODP Hole 146-891A. 8 records from Planktic foraminifera abundance of Hole 54-424. 12 records from Occurrence of mammalia relicts at site Ceremosnica. 452 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/045-9. 65360 records from Museu de Ciències Naturals de Barcelona: MCNB-Cord. 108 records from New records of the family Chalcididae (Hymenoptera: Chalcidoidea) from Egypt. 735 records from Biodiversity Survey of Echuya forest, Year 2012. 1813 records from Distribución potencial del género Ficus (Moraceae) en México. 1333 records from (App 4) Relative contents of benthic foraminifera species in Holocene sediments from Core BP00-07/05. 22977 records from PACA-Fungi - Herbarium Anchieta - Fungi Rickiani. 1640 records from (Table 16) Benthic foraminifera in Eocene-Oligocene sediments of DSDP Hole 90-593. 150 records from Revision of the Agrilus humilis species-group (Coleoptera: Buprestidae: Agrilini) with description of thirteen new species from Southeastern Asia. 77 records from Plantas alimenticias incluidas en la dieta local en el municipio de Montería, Córdoba. 31872 records from Japan Collection of Microorganisms, RIKEN BioResource Center. 137535 records from CNIN/Lepidoptera. 188 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB07 in the euphotic zone of the Aegean Sea in spring 1997. Part 3 - coccolithophores and other groups. 558 records from Herbarium of Lars Levi Laestadius. 2262 records from Larval fish at time series station Helgoland Roads, North Sea, in 2005. 3 records from A new species of Hemiphyllodactylus (Squamata: Gekkonidae) from Hong Kong. 7 records from Foraminifera study in the Horten inner harbor area. 6 records from Two new ovoviviparous species of the family Selachinematidae and Sphaerolaimidae (Nematoda, Chromadorida & Monhysterida) from the northern South China Sea. 146 records from Planktic foraminifera abundance of Hole 2-11. 174 records from Antarctic Euphausiacea occurence data from Polish FIBEX expeditions. 668 records from Assemblage of living benthic foraminifera in sediment core GeoB3712-1. 13 records from Distribution of meiobenthos in sediment core M23_199 (2) of the northeastern Atlantic (Table 1). 151 records from Total foraminifera counts from M35/1_MSN1052. 38 records from Three new species of Onychiuridae Lubbock, 1871 (Collembola, Poduromorpha) from Iran. 2 records from Sclerotinia cirsii-spinosissimi, a new species from the Alps. 60492 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO. 32 records from Planktic foraminifera abundance of Hole 19-184. 452 records from Planktic foraminifera abundance of Hole 32-313. 4 records from High diversity of Caligus species (Copepoda: Siphonostomatoida: Caligidae) in Taiwanese waters. 185 records from (Table 8) Relative abundance of benthic foraminifera in ODP Hole 112-682A, Part I. 4674 records from Data on animal species in the Biosphere Reserve of W Bénin. Data mobilized in the framework of JRS Biodiversity Foundation funded project in Benin. 9081 records from Fiocruz/CCER - Coleção de Ceratopogonidae. 832 records from (Table 13) Late Quaternary planktonic foraminifera in sediments from the Equatorial Indian Ocean. 170 records from Birdrace-Halsbandschnäpper-Stuttgart. 91 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_5-CTD59. 104419 records from Bryophyte Herbarium, Oslo (O-B). 2530812 records from FLORIVON. 624 records from Review of the African genera Arantia Stål and Goetia Karsch (Orthoptera: Tettigoniidae: Phaneropterinae). 2 records from Celaeno detrita. 2119 records from Distribution of planktic foraminifera in sediment core GIK23071-5. 6179 records from (Appendix 2) Stratigraphic distribution of key and potential stratigraphic calcareous nannofossil markers in the upper Campanian–Maastrichtian of ODP Hole 122-762C. 29141 records from Riqueza y distribución de especies vegetales en la Península de Baja California. 118 records from Nannofossil abundance of Hole 9-82A. 1441 records from Données naturalistes de Philippe GOURDAIN (ANVL). 138 records from (Table 2a) Species composition of planktonic foraminiferas in bottom sediments from Core AK6-434-1. 4 records from Planktic foraminifera abundance of Hole 54-421. 42270 records from SIRFF - FNE Centre-Val de Loire - Données 2015. 566 records from Vocalizaciones de aves mexicanas en análisis biogeográficos y reconstrucción filogenética. 317 records from (Appendix A) Calcium carbonate concentrations and accumulation rates of ODP Hole 115-714A. 5390 records from UFRN-Fungos - Herbário UFRN - Fungos. 37 records from A checklist of marine littoral mites (Acari) associated with mangroves. 110558 records from Colección Herbario Federico Medem Bogotá - FMB. 1578 records from Mollusques terrestres de Mayotte : prospections pour l'inventaire des ZNIEFF. 3 records from Species of Macrostomum (Macrostomorpha: Macrostomidae) from the coastal region of Lima, Peru, with comments on M. rostratum Papi, 1951. 164 records from New records of snail-killing flies (diptera: Sciomyzidae) from Iran. 10 records from Three squat lobsters (Crustacea: Decapoda: Anomura) from tropical West Pacific seamounts, with description of a new species of Uroptychus Henderson, 1888. 153 records from Shannon Index and species richness for herbivores. 762 records from Priority effects of early successional insects influence late successional fungi in dead wood. 452 records from SNH Invertebrate Site Condition Monitoring 2013/14: River Spey - Insh Marshes SSSI. 288 records from Taxonomy of the South American genus Pachypops Gill 1861 (Teleostei: Perciformes: Sciaenidae), with the description of a new species.. 66 records from An annotated checklist of earthworms of Greece (Clitellata: Megadrili). 868 records from 5.Tag der Artenvielfalt: Thema Stadtbiotope. 10 records from Two new species of the genus Leeonychiurus Sun & Arbea, 2014 (Collembola: Onychiuridae) from Korea. 2844 records from Reconocimiento de la biodiversidad de la Reserva de la Biósfera Calakmul: Odonata, psocóptera y díptera acuáticos (Insecta). 77 records from GenLink - Genetic diversity of Trifolium repens. 12 records from Occurrence of mammalia relicts at site Seest. 1206 records from Collection of Industrial Microorganisms. 21417 records from Snow Petrel census, Reeve Hill, Windmill Island, East Antarctica (1984-2003). 435 records from Total foraminifera counts of multinet M21/1_MSN611. 564 records from Faberpark (Nürnberg/Stein). 990 records from The South American spider genera Mesabolivar and Carapoia (Araneae, Pholcidae): new species and a framework for redrawing generic limits. 549 records from Vertebrates (except birds, INNS and restricted records), Outer Hebrides. 909 records from (Appendix A3) Planktonic foraminifera of ODP Hole 166-1006A. 1128 records from (Table 1) Distribution of calcareous nannofossils in ODP Hole 113-689B. 162 records from ECOLINC: BIODIVERSITY OF THE WESTERN VOLCANIC PLAINS SIGHTINGS. 7373980 records from Insecta of Costa Rica (INBio). 3 records from A new Schistura from an upper Mekong affluent in Yunnan (Teleostei: Nemacheilidae). 6518 records from Evaluación y monitoreo de manglar en la Reserva de la Biósfera Los Petenes con énfasis en criterios de sustentabilidad y desarrollo. 145 records from Tornoer Teich. 110 records from Revision of the soft scale genus Paralecanium (Hemiptera: Coccomorpha: Coccidae) with the introduction of three new genera and twenty new species. 144 records from Birdrace-NAJU_Aspach-Rems/Murr. 15 records from Revision of the Chinese species of the genus Grouvellinus Champion, 1923 (Coleoptera: Elmidae). The G. acutus species group. 14338 records from Collection of Hymenoptera. 18091 records from Actualización e incremento del banco de datos de la colección de herbario del Jardín Etnobotánico de Oaxaca. 1025 records from (Appendix 2) Absolute abundance of nannofossils in ODP Hole 183-1135A. 571 records from Berlin-Brandenburg Plant Collection 2006. 62 records from Studies in Liocranidae (Araneae): redescriptions and transfers in Apostenus Westring and Brachyanillus Simon, as well as description of a new genus. 76 records from The Oriental species of the ant genus Probolomyrmex (Insecta: Hymenoptera: Formicidae: Proceratiinae).. 258 records from (Table 6) Benthic foraminiferal genera in DSDP Core 95-612-5. 40709 records from DSMZ Prokarya Collection Catalogue. 790 records from Données naturalistes d'IFRECOR (pf). 930 records from (Appendix A4) Planktonic foraminifera of ODP Hole 172-1062B. 4692 records from Westmead Mycology Culture Collection. 266 records from Schellenberg A. 1936. The fishery grounds near Alexandria. Amphipoda Benthonica. Notes and memoirs No 18.. 347 records from Données naturalistes de Delphine MONTAGNE. 90422 records from Global Lacustrine Diatoms. 9446 records from Bird collection of National Museum of Nature and Science. 4 records from New distribution records for the rare genus Afrotremex Pasteels (Siricidae: Hymenoptera) and provision of interactive Lucid identification keys to species. 475 records from Catch related distribution of Appendicularia at station M9_A near the Great Meteor Bank, Northeast Atlantic (Table 7). 423 records from Planktic foraminifera counts of sediment core RC09-162. 10 records from First records of Dentridactylinae (Orthoptera: Tridactylidae) from Colombia, with description of two new species of Dentridactylus Günther. 2476 records from Insect Collection (CeStuBio). 18 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2187-5. 549 records from Total foraminifera counts of multinet M21/2_MSN657. 16 records from A new species of Hedya Hübner from Iran with proposed rearrangement of some species currently assigned to Metendothenia Diakonoff (Lepidoptera: Tortricidae). 184 records from Syndicat_Mixte_de_Défense_des_Berges_de_l'Asse_2017_12_18. 87 records from Phytoplankton abundance at station Sechin_2003-12-10_2, Casma, Peru. 2 records from An integrative description of Ramazzottius subanomalus (Biserov, 1985) (Tardigrada) from Poland. 1992 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during LITTORINA cruise LI1986/1. 255 records from (Table 3) Occurrences of ostracodes in ODP Hole 122-763B. 4788 records from Seed bank grassland. 14 records from Redescription and designation of a neotype for Ophiothrix angulata (Say, 1825) (Echinodermata: Ophiuroidea: Ophiotrichidae). 1 records from Sungei Buloh - Mangrovenwald. 27678 records from (Appendix 3) Assemblage of benthic foraminifera in sediment core M5/2_KL15. 27 records from Sistemática molecular de Trogoniformes (Aves): Filogenia del orden y análisis de variabilidad genética de quetzales en la reserva de la Biosfera El Triunfo. 299 records from (Tables 1-15) Morphometric characteristics of the genus Hinia (Nassariidae, Gastropoda) in the Tertiary of northwest Germany. 194698 records from Naturalis Biodiversity Center (NL) - Micropaleontology. 465 records from Planktic foraminifera counts of sediment core RC09-150. 183 records from Zwei Flüsse - eine Stadt (Villingen-Schwenningen). 779 records from Aportación al conocimiento de la fauna de Ascidias del litoral Pacífico de México. 12766 records from RSPB Reserves breeding bird surveys. 1075 records from Bryopyhtes in forest indices and traits. 2080 records from (Table 10) Distribution of planktonic foraminifers in ODP Hole 112-688A. 32 records from Revalidation of Acanthinozodium Denis, 1966 with description of three new species and discovery of a remarkable male palpal character (Araneae, Zodariidae). 1 records from Two new species of the subgenus Brachyphytodecta Bechyně, 1948 (Coleoptera, Chrysomelidae, Gonioctena) from Sichuan, Southwest China. 40316 records from Clyde Breeding Bird Tetrad Atlas 1985 - 1991 - non-sensitive species. 51 records from Meiofauna abundance in sediment core 12930-029. 126 records from Hochschule Zittau/Görlitz. 87220 records from SBC LTER Darwin Core Archive: Kelp Forest Reef Fish Abundance. 330 records from Nannofossil abundance of Hole 24-235. 1734 records from pflanzendiversitaet_2008_sch_alb_hai_aktualisiert. 303 records from CNAN/Escorpiones Estado de Mexico. 1254 records from Estado actual del conocimiento biológico de algunas especies de roedores de las familias Muridae, Geomyidae, Heteromyidae y Sciuridae (Rodentia: Mammalia) incluidas en el PROY-NOM-059-ECOL-2000. 12 records from Multivariate discrimination and description of a new species of Tapinoma from the Western United States.. 43 records from Three new species of the Encarsia inaron (Hymenoptera: Aphelinidae) species group from China with a key to Chinese species. 46 records from AKG-Gelände in Bensheim. 27 records from AMF Colonization VIP 2008 Rillig. 538 records from Occurrence of mammalia relicts at site Velika Pecina. 12 records from Three species of Hydrobaenus Fries (Diptera: Chironomidae: Orthocladiinae) from Belarus. 88 records from Planktic foraminifera abundance of Hole 19-188. 207364 records from NRW Regional Data: all taxa (excluding sensitive species), West Wales. 116417 records from Michigan State University Herbarium Lichens. 115 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-04, >125 µm fraction. 22 records from Thorectinae (Porifera: Demospongiae: Dictyoceratida) from Northeastern Brazil: two new species and transfer of Scalarispongia cincta (Boury-Esnault, 1973) to the genus Thorecta Lendenfeld, 1888. 80 records from Range table from benthic foraminifers in ODP Hole 144-873B. 199 records from Evaluación de la resistencia a la roya (Uromyces appendiculatus) en poblaciones silvestres y cultivadas de frijol, mediante el empleo de marcadores genéticos moleculares. 656 records from Uso y monitoreo de los recursos naturales en el Corredor Biológico Mesoamericano (áreas focales Xpujil-Zoh Laguna y Carrillo Puerto). 42 records from Sarcodine counts and carbon biomass at station TT012_5-PMOC8. 14 records from New species and new behavioral data of Phlugiola Karny, 1907 (Orthoptera: Tettigoniidae: Meconematinae) from the Brazilian Amazonian Rainforest. 12 records from A new genus and five new species of Astieae (Araneae: Salticidae) from Australia, with remarks on distribution. 136 records from Phytoplankton abundance at station Casma_2003-04-14_1, Casma, Peru. 14064 records from FBIP: Systematics of South African Hymenoptera. 14 records from ZUEC-BRA - Coleção de Brachiopoda do Museu de Zoologia da UNICAMP. 3758 records from HBRG Badger Dataset. 583 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE262. 7491997 records from Florabank1 - A grid-based database on vascular plant distribution in the northern part of Belgium (Flanders and the Brussels Capital region). 19 records from Range table from benthic foraminifers in ODP Hole 189-1172D. 5 records from New species and synonymy in the genus Corotoca Schiødte, 1853 (Coleoptera, Aleocharinae, Corotocini). 12 records from Integrative taxonomy of Hemimycale (Hymedesmiidae: Poecilosclerida: Demospongiae) from Southeastern Brazil, with the description of two new species. 90 records from Flusswerder in der Weser (Hameln). 130 records from SNH Invertebrate Site Condition Monitoring 2015: Mount Bog SSSI. 50490 records from Computarización de la Colección Nacional de insectos Dr. Alfredo Barrera Marín del Museo de Historia Natural de la Ciudad de México. 7285 records from Live (Rose Bengal stained) benthic foraminifera of surface sediments of the Persian Gulf (Table 1). 521 records from Planktic foraminifera counts of sediment core V19-201. 12 records from On The Relationships of the Spider Genus Cybaeodes (Araneae, Dionycha). 61 records from Population status, Distribution and Threats to the Nile lechwe (Kobus megaceros, M.T.Von Heuglin,1853) in the Sudd Wetland, South Sudan (2012). 6 records from Unraveling a new lineage of Hydrobiidae genera (Caenogastropoda: Truncatelloidea) from the Ponto-Caspian region. 1344 records from Japanese Knotweed Records in the Isle of Man 1991-2008 - Department of Environment, Food and Agriculture (DEFA).. 78 records from Navigator, a new endemic genus of Cetoniinae (Coleoptera: Scarabaeidae) from Australia, with descriptions of two new species and behavioural studies. 28 records from A new endemic species of Willowsia from Florida (USA) and descriptive notes on all New World Willowsia (Collembola: Entomobryidae). 4160 records from Non Native Species Across Wales (1989 to 2012). 359 records from Occurrence of mammalia relicts at site l´Abri du Pont d´Ambon. 1452 records from (Appendix Table 3) Number of planktonic foraminiferal specimens within species in Late Creatceous sediments of ODP Hole 122-762C from the Exmouth Plateau, eastern Indian Ocean. 1404 records from Factual Database of Native Flora Seeds in Korea. 94 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/042-2. 476 records from Seven new species of Spathidexia Townsend (Diptera: Tachinidae) reared from caterpillars in Area de Conservación Guanacaste, Costa Rica. 848 records from The types of Phasmida in the Natural History Museum, London, UK. 3068 records from PonTaurus collection. 1840 records from (Table 8) Distribution of planktonic and selected benthic foraminifers from DSDP Hole 87-584. 20414 records from Auckland Museum NZ Marine Collection. 1614 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V29-179. 2105 records from Acari Collection - Instituto Nacional de Pesquisas da Amazônia. 4 records from A new skate genus Orbiraja (Rajiformes: Rajidae) from the Indo-West Pacific. 4942 records from BOTUw - Xiloteca "Profa. Dra. Maria Aparecida Mourão Brasil". 285 records from Fig. 7. Relative abundance of ostracod species in composite core JH05. 1 records from Description of Tottonophyes enigmatica gen. nov., sp. nov. (Hydrozoa, Siphonophora, Calycophorae), with a reappraisal of the function and homology of nectophoral canals. 1149 records from Benthic foraminifera distribution of sediment core ASV11-987 (ASV987). 4 records from One new species of the genus Xizicus (Orthoptera: Tettigoniidae: Meconematinae) from Chongqing, China. 8 records from Two new species of cave-dwelling Charinus Simon, 1892 from Brazil (Arachnida: Amblypygi: Charinidae). 150 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - BIRDRACE *Ckassine*. 70 records from Nannofossil abundance of Hole 6-57A. 197 records from Range table from ostracoda in ODP Hole 159-960C. 78 records from The genus Acellomyia González, a new taxonomic arrangement of its species and descriptions of a new genus and two new species from southern South America (Diptera: Tabanidae: Diachlorini). 14156 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 78 records from Phytoplankton abundance at station Casma_2003-02-27_1, Casma, Peru. 46 records from UWIZM Turtles and Crocodilians. 52 records from Répertoire des espèces de poisson inventoriées dans le fleuve Niger, de Niamey à Say. 1472 records from Census of plant species in forest gaps in the natural forest of Massi (Lama Forest reserve, South-Benin). 206 records from Studies on neotropical Phasmatodea XVII: Revision of Phantasca Redtenbacher, 1906, with the descriptions of six new species (Phasmatodea: Diapheromeridae: Diapheromerinae). 1682 records from Flora of Westgate Park - Photos from Lyn Allison. 7 records from The taxonomic and phylogenetic status of some poorly known Anolis species from the Andes of Colombia with the description of a nomen nudum taxon. 3150 records from Relative abundance of organic-walled dinoflagellate cysts in surface sediments. 123 records from Range table from planktonic foraminifers in ODP Hole 146-892D. 122 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/567-1. 54 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-18-1. 13 records from A new species of the genus Phytoecia Dejean, 1835 (Coleoptera: Cerambycidae) from Greece. 21 records from (Table 3) Paleotemperature estimates for ODP Hole 105-646B. 2543 records from Diversidad y riqueza vegetal de los substratos rocosos del centro del estado de Veracruz. 309 records from Phytoplankton abundance at bottle station GOM3/1. 2318 records from Range table from planktonic foraminifers in ODP Hole 157-954B. 2 records from Pelops phaeonotus. 28 records from Planktic foraminifera abundance of Hole 20-199. 4809 records from Abundance of coccoliths in sediment core GeoB1710-3. 1515 records from Abundance of phytoplankton, heterotrophic nanoflagellates and bacteria through the water column at time series station L4 in the Western English Channel in 2009. 2 records from Begonia jaguarensis L. Kollmann, R. S. Lopes & Peixoto (Begoniaceae), a new species from North of Espírito Santo State, Brazil. 3154 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V22-38. 289 records from Planktic foraminifera abundance of Hole 24-233. 14 records from Inventario Herpetológico Pauto J, Rincón del Soldado, Yopal, Casanare. 118 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2010. 28 records from Descriptions of new and little-known land snail taxa from Turkey, and establishment of a new genus (Gastropoda, Pulmonata: Lauriidae, Enidae and Vitrinidae). 12457 records from HBRA - Herbário do Instituto de Estudos Costeiros da Universidade Federal do Pará. 62 records from Diatom abundance of Hole 60-453. 341 records from Size of planktic foraminifera at CTD station PS55/019. 1810 records from 2003-2004 Wokingham WHS Surveys. 552 records from Colección Mastozoológica de la Universidad Distrital Francisco José de Caldas. 57 records from Occurrence of mammalia relicts at site Vraona Cave. 1014 records from RHS Hemerocallis midge survey. 4428 records from (Table 10) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-712A. 667 records from Pollen analysis of sediment profile WE from Wesslinger See. 486 records from Point Pelee National Park Collection, Canada. 142 records from Cabinet_Barbanson_Environnement_2017_12_18. 4 records from Shewanella marisflavi sp. nov. and Shewanella aquimarina sp. nov., slightly halophilic organisms isolated from sea water of the Yellow Sea in Korea. 52 records from Akysis pulvinatus, a new species of catfish (Siluriformes: Akysidae) from southern Thailand.. 475537 records from Some Plant Specimens from KUN, IBSC, NAS Herbarium in China from 1900 to 1950. 447 records from Mammalia - Baekdu Mountain Animal (KIDR-MM). 37918 records from Herbarium Specimens of Bonin and Ryukyu Islands. 11647 records from Planktic foraminifera counts of sediment core MD95-2040. 24 records from Results of palynological analysis of Hole 302-M0004B. 493 records from Total foraminifera counts from multinet SO119_MSN1286. 5949 records from CeDoc de Biodiversitat Vegetal: BCN-Lich. 138 records from Revision of the subgenus Aulacomyrma Emery of the genus Polyrhachis F. Smith, with descriptions of new species.. 8 records from Simpsonichthys nielseni sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual killifish from the São Francisco River basin, Brazil.. 128 records from Reuniting males and females: redescriptions of Nuisiana arboris (Marples 1959) and Cambridgea reinga Forster & Wilton 1973 (Araneae: Desidae, Stiphidiidae). 10574 records from Protected species bycatch in New Zealand fisheries. 6075 records from MfN - Diptera Collection. 222 records from Occurrence d'ongulés et Lagomorphes de l'association Coordination Mammalogique du Nord de la France (CMNF). 6 records from Cobitis nalbanti, a new species of spined loach from South Korea, and redescription of Cobitis lutheri (Teleostei: Cobitidae). 144 records from Total foraminifera counts of multinet M21/5_MSN733. 7739 records from (Figure 13) Distribution of middle Miocene through middle Pleistocene planktonic foraminifera in ODP Hole 132-810C. 101 records from Coccolith counts of multinet M32/5_MSN979. 70 records from Zanobatus maculatus, a new species of panray from the Gulf of Guinea, eastern central Atlantic (Elasmobranchii: Batoidea: Zanobatidae). 217 records from Occurrence of mammalia relicts at site l´Abri des Battuts I. 478 records from Parásitos de peces nativos de cenotes de la Península de Yucatán, un ecosistema único en México. 8525 records from Literary descriptions of Iranian lizards. 6 records from A new species of Stenchaetothrips (Thysanoptera, Thripidae) from Bamboo, based on morphological and molecular data. 2 records from A new species of gall midge (Diptera: Cecidomyiidae) damaging ornamental Callistemon (Myrtaceae) in Australia. 281402 records from Natural History Museum Rotterdam (NL) - Insecta collection. 1654 records from (Table 16B) Occurrences of planktonic foraminifers in DSDP Holes 90-594 and 90-594A. 467 records from (Table 4) Standing stock values of important species in surface sediments. 188 records from (Table 2) Biomass of benthos and different animal groups in the Scotia Sea. 10 records from Distribution of Quinqueloculina sp. in sediment core 13077-087. 53650 records from Données Opie, Coléoptères saproxyliques. 340 records from Revision of the funnel-web spider genus Novalena (Araneae: Agelenidae). 64 records from Nannofossil abundance in sediment core PS1312-4. 266 records from Abundance of radiolaria at station LV28-4-1. 7691 records from Distribución y abundancia de aves marinas y acuáticas en regiones marinas prioritarias y áreas protegidas del Golfo de California y Golfo de México. 120 records from UWIZM Echinoderms. 2400 records from (Table T2) Biostratigraphy of calcareous nannofossil taxa in ODP Hole 183-1136A. 456 records from Phytoplankton abundance at bottle station GOM6/1. 12 records from A new genus of nesticid spiders from western European Peninsulas (Araneae, Nesticidae). 772 records from Mammal specimens of Kawasaki Municipal Science Museum. 78 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_11-CTD132. 100 records from Microorganismos asociados con la filósfera de plantas de Espeletia en el PNN los Nevados. 2 records from Carabodes coriaceus. 84 records from Schulgarten Paul-Schneider-Schule, Münster. 18 records from New Oriental genera in the family Issidae (Hemiptera: Fulgoromorpha). 14043 records from DASSH Data Archive Centre volunteer sightings records. 48 records from Tauchen und Meer. 228 records from An annotated checklist of the Chilopoda and Diplopoda (Myriapoda) of the Abrau Peninsula, northwestern Caucasus, Russia. 787 records from Abundance of phytoplankton, heterotrophic nanoflagellates and bacteria through the water column at time series station L4 in the Western English Channel in 2008. 1282 records from Códigos de barras de helmintos de anfibios y reptiles de México. 230730 records from TTU Mammals Collection. 47 records from New species and additional data on the chewing louse genus Myrsidea (Phthiraptera: Menoponidae) from wild Neotropical Passeriformes (Aves). 2386 records from Biological data from the Soviet Antarctic Expedition (1955-1958). 112 records from Planktic foraminifera counts of sediment core RC17-113. 20294 records from Relative abundance of planktic foraminifera in sediment core GeoB1309-2. 5 records from Persianorchestia, a new talitrid genus (Crustacea: Amphipoda: Talitridae) from Gulf of Oman, Iran. 8 records from Yunnanosticta gen. nov., from Yunnan, a new genus from the Sinostictinae, with the description of two new species (Odonata: Zygoptera: Platystictidae). 268 records from Birdrace-Easy_Birders-Plön. 720 records from Total foraminifera counts from multinet M31/3_MSN913. 60 records from bmhs_echinoderm_collection. 36 records from Alpheus luiszapatai, a new species of rare and colorful deep water alpheid shrimp (Crustacea: Decapoda: Alpheidae) from Arusí, Chocó Department, Pacific Coast of Colombia. 713 records from (Appendix 4) Stable oxygen isotope record of Globigerina bulloides and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD95-2040. 797 records from (Table1) Living and dead benthic foraminifera abundance in sediments of the Bottsand-Lagoon, Western Baltic Sea. 16 records from A revision of the genus Lepidobrya Womersley (Collembola: Entomobryidae) based on morphology and sequence data of the genotype. 42 records from New species and records of Perlidae (Plecoptera) from Espírito Santo State, Brazil. 802 records from A review of the North American species of the fungus-gardening ant genus Trachymyrmex (Hymenoptera: Formicidae).. 470 records from Pseudoscorpions of Ireland. 348 records from Inventario Nacional de Candelilla (Euphorbia antisyphilitica) Fase I.. 110 records from A taxonomic revision of the Pheidole roosevelti-group (Hymenoptera: Formicidae) in Fiji.. 29751 records from Société_Française_d'Odonatologie_2017_12_18. 493 records from Total foraminifera counts of multinet M21/6_MSN776. 19508 records from Universidad Politécnica de Madrid, Dpto. Biología Vegetal, Banco de Germoplasma. 17 records from Two new species of armoured spiders from Vietnam and Cambodia (Araneae: Tetrablemmidae: Pacullinae). 1384 records from Planktic foraminifera abundance of Hole 34-319. 4 records from Die Myriopodenfauna von Albanien und Jugoslavien. 1936 records from FBIP: Offshore Benthic Macrofauna Data. 14 records from Revision of the genus Hormoserphus Townes, 1981 (Hymenoptera: Proctotrupidae), with description of Trachyserphus gen. n. and a new species. 1022 records from Plantas del municipio El Carmen de Chucurí, Santander - Proyecto Santander BIO. 3118 records from Polychaetes in surface sediments off Sylt collected during HEINCKE cruise HE258. 83968 records from Repatriación de datos de los lepidópteros depositados en la Colección del McGuire Center for Lepidoptera and Biodiversity, Florida Museum of Natural History. 14640 records from Aves Collection of Institute of Systematics and Evolution of Animals. 23487 records from Universidad Autónoma de Madrid, Biología, Acalypha. 2 records from Données naturalistes de Marcel CRUVEILLIER. 12170 records from Herbarium specimens of CBNA (GAP). 502 records from Weinberg Reichersdorf. 8 records from Distribution of Quinqueloculina sp. in sediment core 12930-084. 4960 records from Abundances of organic-walled dinoflagellate cysts in sediment core GeoB5546-2. 12484 records from Natural history museum data on Canadian Arctic marine benthos. 8534 records from Relative abundance of planktic foraminifera in sediment core GeoB1523-1. 1 records from A new species of Sweltsa (Plecoptera: Chloroperlidae) from Sichuan Province of southwestern China. 42 records from Occurrence of mammalia relicts at site Kogelstein. 1225 records from (Table T5) Benthic foraminifer occurrence in ODP Hole 183-1139A sediments. 22 records from Données de Lépidoptères de Bruno DAUGET - Dépt du LOIR-ET-CHER (41). 330 records from Pollen analysis of sediment profile NI0 from Niklassee. 70951 records from Herbarium specimens of Société des Sciences Naturelles et Mathématiques de Cherbourg (CHE). 341207 records from CONN. 12299 records from ISM Mammalogy Collection. 221314 records from The avian collection at the Natural History Museum, Oslo, Norway. 130 records from (Table 15) Distribution of ostracode species in Core PS51/135-4. 345 records from Plasm bearing foraminifera counts of multinet M21/1_MSN614. 158 records from (Table 1) Benthic foraminiferal distribution at ODP Site 127-794. 39 records from Nothocasis rosariae sp. n., a new sylvicolous, montane species from southern Europe (Lepidoptera: Geometridae, Larentiinae). 4670 records from Données du programme 50000 observations pour la forêt. 2 records from Studies in Guatemalan Ensifera: Mayacephalus (Orthoptera: Tettigoniidae) a new cone-headed katydid genus. 3167 records from (Appendix B) Stratigraphic occurrence of radiolarian special and species groups in sediments of ODP Hole 199-1218A. 31 records from Projekt Wahner Heide. 2730 records from ACCDC: Rare Species in Atlantic Canada and Adjacent Marine Waters. 379 records from (Table 1) Abundance of the main species of benthic Foraminifera in the assemblage Cribrostomoides subglobosus-Tritaxis nana of the Kara Sea. 392 records from Inventaire malacologique du site Natura 2000 FR9301547 du Grand Coyer (2007, ONF/MNHN). 203 records from Occurrence datasets of Freshwater Snails (Gastropoda) of Kenya mobilized from the Zoological Collection of National Museums of Kenya, Nairobi and Literature. 97 records from Planktic foraminifera assemblage in sediment core GIK23246-2. 2 records from Zetes lucorum. 141 records from (Table 2) Dissolution index (XDX) values and average test mass for four species of planktonic foraminifera. 1567 records from Collection Arachnida - ZSRO. 268 records from Woodland Survey. 9490 records from Collection botanique Le Grand A. (BOUM). 1240 records from Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert sowie Umland. 19577 records from HBRG Other invertebrates Dataset. 71 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-03, 63-125 µm fraction. 74 records from Cyanobacteria of Algal Collection of Soil Science Institute (ACSSI). 26 records from Review of the genus Cyrtosia Perris (Diptera: Mythicomyiidae: Platypyginae) in Iran, with description of three new species. 108 records from New records of Gerromorpha and Nepomorpha (Insecta: Hemiptera: Heteroptera) from South America. 478 records from Nannofossil abundance of Hole 10-95. 2682 records from CNAN/Arañas sinantrópicas. 2273 records from Macro benthos in surface sediments sampled during POLARSTERN cruise ANT-XXIII/8. 21663 records from Monitoring data from the federal state Saxony-Anhalt (Germany). 18 records from A new species of the genus Aphanius (Nardo, 1832) (Actinopterygii, Cyprinodontidae) from Algeria.. 1368 records from SEWBReC Algae and allied species (South East Wales). 2422 records from CSIRO, Cruise SS199101, Marine Biology Data, Western Australia, 1991. 13 records from Distribution of Quinqueloculina sp. in sediment core 13200-078. 188 records from Faunal assemblage of sediment core TR149-35. 17856 records from City of Amsterdam (NL) - Fyke Fishing Piet Ruiter. 11745 records from (Table 5) Stratigraphic distribution of calcareous nannofossil taxa in ODP Hole 149-898A. 215 records from Occurrence of mammalia relicts at site Laugerie-Haut e-Ouest. 19 records from Inventario de Aves Pauto J, Yopal, Casanare. 52750 records from Provincial Museum of Alberta, Edmonton, AB, Canada. Birds (Aves). 168 records from (Table 2) Absolute abundance of Contusotruncana contusa in DSDP Hole 72-516F. 14 records from Nannofossil abundance of Hole 31-298A. 46664 records from Fife non-breeding bird 5km atlas 1991-99. 190232 records from Diversidade e ocorrência de peixes em Inhambane (2009-2017). 2444 records from (Figure 9) Distribution of Cretaceous planktonic foraminifers and associated organisms from DSDP Hole 77-536. 1473 records from (Table A.08) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 1-3 (80-150 µm). 244 records from (Table 1) Abundance of planktonic foraminifera in ODP Hole 113-689B, large size fraction. 1373 records from Echinoderm specimens of Ryukyu University Museum (Fujukan). 5246 records from SPC CoFish Fish Observations Niue 2005. 1 records from Description of a new species of Lutosa Walker, 1869 (Orthoptera: Anostostomatidae: Lutosinae) from the Brazilian Atlantic Forest, with biological and behavioral information. 1769 records from Distribution of benthic foraminifera in DSDP Hole 24-238 in the Central Indian Ocean (Appendix A). 12 records from The Hydraenidae of Cuba (Insecta: Coleoptera) III. Description of two new hygropetric species of Hydraena Kugelann. 2 records from A new species of genus Eulimnadia Packard, 1874 (Branchiopoda: Spinicaudata: Limnadiidae) from India with an updated key for some Indian species. 319841 records from The molluscs collection (IM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 2 records from Synthèse de la Répartition des populations de cerf élaphe en 1995 (réseau Ongulés sauvages ONCFS-FNC-FDC). 87 records from Description of the new genus Nebulene Volynkin & Černý, gen. nov., with a new species from Thailand and Vietnam (Lepidoptera, Erebidae, Arctiinae). 734 records from ARKO. 2270 records from Esponjas, corales escleractinios, equinodermos y peces de arrecifes coralinos del norte y sur de Veracruz. 39660 records from Atlas of Life in the Coastal Wilderness - Sightings. 770 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Laridae. 4 records from Description of a new species of Miltochrista Hübner from Vietnam, with eight new combinations (Lepidoptera, Erebidae, Arctiinae). 780 records from Gipuzkoako Foru Aldundiaren Landareen Germoplama Bankua / Banco de Germoplasma Vegetal de la Diputación Foral de Gipuzkoa. 8 records from A review of the Arcuphantes species with the genitalia of arcuatulus - type (Araneae, Linyphiidae). 5649 records from USGS South Florida Fish and Invertebrate Assessment Network Harvest. 265 records from Meiobenthic taxon counts from deep-sea in situ recolonization experiment II deployed at station PS64/475-1 during ARK-XIX/3c. 41499 records from Bottom Trawl Surveys: Catch and Effort Data For South East Australia, 1898-1996. 243 records from (Table 1) Oligocene benthic foraminifers abundance in ODP Hole 124-767B. 2090 records from Nannofossil abundance of Hole 49-407. 80 records from Catálogo de maíces nativos generada en la tesis El sistema milpa y sus recursos fitogenéticos en Santa María Tlahuitoltepec, Oaxaca. 53 records from Benthic foraminifera and phytodetritus species in sediments from DSDP Site 85-573. 5361 records from CHAS Mammalogy Collection (Arctos). 1059 records from UAM Herpetology Collection (Arctos). 106 records from Range table from benthic foraminifers in ODP Hole 139-856A. 6231 records from Distribution of dinoflagellate cysts in Eocene-Oligocene sediments of DSDP Hole 38-338. 2001 records from Abundance of nanoplankton in sediment core GeoB1028-5. 262 records from Benthic foraminifera abundance of Hole 56-435A. 62 records from (Table 4) Foraminiferal species in DSDP Sample 78-541-8-3,141-143 and Section 78-541-8-CC. 6 records from Benthic macrofauna abundance of sediment core 12930-022. 143 records from (Table T2) Occurrence of Lower Cretaceous planktonic foraminifera in ODP Hole 171B-1049B. 35 records from (Table 3) Neogene relative abundances of Uvigerina spp. at DSDP Hole 95-613. 6 records from A new species of the genus Leptobrachium (Anura: Megophryidae) from the Gaoligongshan Mountain Range, China. 8 records from New country records of reptiles from Laos. 254 records from BIRDRACE VdW Wilder Westen. 1467 records from Galapagos grasses and sedges. 621 records from Données naturalistes de Noëlie TAPKO. 6 records from Rediscovery of Chaetostomus setosus Boulenger 1887 (Siluriformes, Loricariidae), and assessment of the external characters used for determination of genera within the Chaetostoma group. 5630 records from Helgeland Museum, Araneae. 4558 records from (Table 5) Ranges of benthic foraminifers from the late Oligocene to the early Miocene in ODP Hole 115-714A. 1310 records from Data collected on animal species through census using Kilometric Abundance Index (KAI) in Biosphere Reserve of W-Bénin. Data mobilized in the framework of JRS Biodiversity Foundation funded project in Benin. 355528 records from Marie-Victorin Herbarium (MT) - Plantes vasculaires. 139 records from Total foraminifera counts of multinet M21/4_MSN703. 110 records from (Table 5) Live benthic foraminifera in sediment core SO130-236MC. 113454 records from Banc de dades de biodiversitat de Catalunya-FungaCat. 160 records from BIRDRACE Die Göttinger Sozialbrachvögel. 12520 records from Borders Backyard Biodiversity. 130 records from Taxonomic revision of the Protopolybia sedula species-group (Hymenoptera, Vespidae, Polistinae), with an new identification key to species. 24 records from (Table 1) Stage of the lemming cycle and nesting parameters of the greater snow geese between 1996-2005, Bylot Island. 1 records from A new species of direct-developing frog of the genus Pristimantis (Anura: Terrarana: Craugastoridae) from Cordillera del Cóndor, Ecuador, with comments on threats to the anuran fauna of the region. 398 records from (Table 3) Relative abundances of benthic foraminifera in ODP Hole 105-646A. 82 records from Wälder im Hainbachtal. 37764 records from Insect specimens of Nasunogahara Museum. 4 records from Alpheus naranjo, a new brightly coloured snapping shrimp from the Caribbean coast of Panama (Malacostraca, Decapoda, Alpheidae). 282 records from Pollen data of trap CB1. 106 records from (Table III) Abundance of crustacea orders during RSS James Clark Ross cruise JR144. 84 records from Pseudecheneis suppaetula, a new species of glyptosternine catfish (Teleostei: Sisoridae) from India.. 366 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1359. 552 records from Phytoplankton abundance at station CD46_0405C#7. 2 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 15 records from Larval morphology of benthic and interstitial water mites (Acari: Hydrachnidia) from a Luxembourgian stream. 38 records from SANBI: Mozambique Sky Islands-Reptile Survey. 111209 records from USGS South Florida Fish and Invertebrate Assessment Network Braun Blanquet. 1054 records from Range table from benthic foraminifers in ODP Hole 145-887A. 59 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/011-3. 23 records from Bilder der Natur. 3 records from A second species of the genus Blythia Theobald, 1868 (Squamata: Colubridae) from Mizoram, India. 6 records from Racekiela andina sp. nov. (Spongillida: Spongillidae): first report of a freshwater sponge from the Venezuelan Andes. 2186 records from (Table 3) Distribution of planktonic and selected benthic foraminifers from DSDP Hole 87-583. 2479 records from Planktic foraminifera counts of sediment core A180-15. 10 records from A new species of Phaenostoma d’Orchymont, 1937 (Coleoptera: Hydrophilidae) from Brazil. 620 records from Digitalización de la colección FITO-UBIPRO, de las enfermedades y sus agentes causales, de los cultivos agrícolas de la región centro de México. 70749 records from The birds collection (ZO) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 4 records from Systematic position of two Pliocene carditids with description of Akardita n. gen. and A. iberica n. sp. (Bivalvia: Carditidae). 140 records from Corvids Literature Database. 238 records from Ophion scutellaris species group specimen data. 14 records from City of Edinburgh Natural Heritage Service - Bumblebee Walk. 20558 records from Liste des récoltes par Herbier de dépôt TOGO. 370 records from Klasse 3a. 276 records from Código de barras de ocho complejos de especies de aves mexicanas. 32 records from Microplankton abundance at Station MARCH-1997-GN36199704603MNB03 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms. 48 records from Kaisertal. 104 records from Status and spatial diversity of Sorghum wild species in Malawi.. 56548 records from ATBI Parc national du Mercantour / Parco naturale Alpi Marittime. 184 records from Birdrace-Team_BO-bachter-Bochum. 3220 records from Observations issues des suivis de phoques en France métropolitaine du laboratoire LIENSs. 762 records from Cretaceous nannofossils in profile Serre Chaitieu, SE France. 817937 records from BugGuide - Identification, Images, & Information For Insects, Spiders & Their Kin For the United States & Canada. 8 records from Two new species and new records of the genus Parachironomus Lenz, 1921 (Diptera, Chironomidae) from northern Russia. 3300 records from University of Calgary Herbarium. 63832 records from Phytopathogenic Fungi Observed by Hans and Hanna Doppelbaur. 11 records from A Cryptic Invasion in the Western Atlantic: Presence of the Fouling Barnacle Megabalanus zebra (Darwin, 1854) (Crustacea, Cirripedia) in the Caribbean Sea. 34 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC09. 546018 records from SER Site-based Surveys. 2 records from A case of disjunct montane linyphiid species (Araneae) in the Palaeotropics, with notes on synonymy and the description of a new species. 52 records from A new species of Oreodera Audinet-Serville, 1835 from Ecuador (Coleoptera, Cerambycidae, Lamiinae) and new geographical records. 288 records from Range table from planktonic foraminifers in ODP Hole 154-929E. 2 records from Battling the un-dead: the status of the Diptera genus-group names originally proposed in Johann Wilhelm Meigen’s 1800 pamphlet. 4 records from Description of a new genus and two new species of alpheid shrimps from Guam (Crustacea, Decapoda) *. 990 records from Micromycetes of vascular plants of the Nurata Nature Reserve, Uzbekistan. 617 records from Benthic foraminifera assemblages and stable isotopes of sediment core PS2458-4. 11024 records from Vascular Plants Collection of National Museum of Nature and Science. 366 records from Occurrence of mammalia relicts at site l´Abri de la Ferrassie. 4006 records from Planktic foraminifera abundance of Hole 80-548. 2267 records from Araneae_Raw1. 6 records from Emschermannia ramificata - a new genus and species of solitary entoproct from the Kara Sea, Russia. 28946 records from Entomology at ZMUC, Natural History Musem of Denmark. 47176 records from Condition of rocky reef communities around Tasmania: invertebrate surveys, Australia (1992-1995 and 2006-2007). 2243 records from Florística y biogeografía de algunos bosques mesófilos de la Huasteca Hidalguense: Fase I (Tenango de Doria y Tlanchinol). 100 records from Phytoplankton abundance at station Rigel_6_2005-02 in Febraury 2005, Chipana, Chile. 117 records from Total foraminifera counts of multinet M21/4_MSN710. 3616 records from University of Amsterdam (NL) - Páramo vegetation research, Ecuador.. 69 records from Phytoplankton counted in three surface sediment samples from the South Atlantic at station PS2230-1, PS2367-1 and PS2376-2. 20 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B2_832-16. 98 records from Schulgartengelände des Hans-Carossa-Gymnasiums (Berlin). 5879 records from The Erysiphales Collection at the University Halle-Wittenberg. 121 records from (Table 2) Distribution of Upper Cretaceous agglutinated benthic foraminifers in DSDP Hole 20-198A. 321 records from Occurrence of mammalia relicts at site l´Abri de Combe-Cullier. 18 records from Kryptopterus platypogon, a new silurid catfish (Teleostei: Siluridae) from Borneo.. 1196 records from (Table 1) Relative abundances of calcareous nannofossils in ODP Hole 115-711A. 4 records from Two new species of the genus Chibiraga Matsumura, 1931 (Lepidoptera: Limacodidae) from China. 53 records from Range table from planktonic foraminifers in ODP Hole 183-1135A. 2346 records from Mollusca specimens of Manazuru Shell Museum. 4746 records from Observations de Mammifères marins. Globice Réunion 2009-2013. 1776 records from Jeu de données convention CD78-SPN-2014-2015. 326 records from Total living benthic foraminifera at station M33/1_MC-03 (NAST), size fraction >30 µm. 7742 records from Insect specimens of Kushiro City Museum. 795 records from Mooswald (Freiburg). 9897 records from Malezas introducidas en México. 29653 records from Arachnologie - SMNG. 234 records from Phytoplankton abundance at station Rigel_4_2005-07 in July 2005, Chipana, Chile. 272 records from Nannofossil abundance of Hole 55-430A. 49460 records from Osaka Prefectural Minoh Park Insects Museum. 358483 records from RECORD Butterfly Data. 518 records from Nannofossil abundance of Hole 15-153. 1594 records from DREAL Auvergne - Mammifères - 2015. 5 records from A checklist of Indian armored spiders (Araneae, Tetrablemmidae) with the description of a new species from the Western Ghats. 1383 records from Fiocruz/COLTRYP - Coleção de Trypanosoma de Mamíferos Silvestres, Domésticos e Vetores. 781 records from Inventario de Aves y Mamíferos en humedales del departamento de Córdoba. 732 records from Invertebrate collection. 2 records from Synthèse de la Répartition des populations d'isard en 1994 (réseau Ongulés sauvages ONCFS-FNC-FDC). 36 records from Feather mites of the subfamily Proctophyllodinae (Acari: Proctophyllodidae) from passerines (Aves: Passeriformes) in Costa Rica. 224 records from Megafauna of the UKSRL exploration contract area and eastern Clarion-Clipperton Zone in the Pacific Ocean: Echinodermata. 9 records from Distribution of Quinqueloculina sp. in sediment core 13200-081. 18 records from (Table 1) Lipid and organochlorine content in blood of common eiders (Somateria mollissima) in Svalbard. 14 records from Bodotria jejuensis sp. nov. (Crustacea, Cumacea, Bodotriidae), a new Korean cumacean. 530 records from Planktic foraminifera abundance of Hole 73-521. 86 records from Bryconops magoi and Bryconops collettei (Characiformes: Characidae), two new freshwater fish species from Venezuela, with comments on B. caudomaculatus (Gunther).. 291 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1383. 174 records from BIRDRACE Unterste Niederrhein-Rennvögel. 64 records from The genus Arocatus in Taiwan (Hemiptera: Heteroptera: Lygaeidae). 81 records from In the footsteps of history: the bees of the genus Hylaeus Fabricius (Hymenoptera, Apoidea: Colletidae) collected by V. I. Roborovsky and P. K. Kozlov in Northwest China (1895 - 1926). 2 records from A new species, new synonymy and new records of Mexican and Central American Xyleborini (Coleoptera: Curculionidae: Scolytinae). 101 records from Phytoplankton abundance at station Casma_2003-06-24_2, Casma, Peru. 2177614 records from Atlas of Finnish Macrolepidoptera. 78 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Phoenicopteridae. 107 records from BIRDRACE leucorhö statt logorrhö. 3931 records from Nannofossil abundance of Hole 15-147. 7857 records from (Appendix A) Stratigraphic range and relative abundance of Neogene planktonic foraminifer taxa in ODP Hole 120-747A. 141 records from Macrohongos de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 90 records from Excavating sponges from the Pacific of Central America, descriptions and a faunistic record. 5953 records from SPFw - Xiloteca do Instituto de Biociências da Universidade de São Paulo. 19228 records from University of British Columbia Botanical Garden Collections (UBCBG). 2 records from Dinoflagellate abundance of Hole 21-207A. 28826 records from Catálogo y base de datos preliminar de la flora de Sinaloa. 449 records from (Table 6) Benthic foraminiferal community at DSDP Hole 94-611C. 36657 records from Plant Specimen from Herbarium (LBG) in China, Lushan Botanical Garden, Jiangxi and Chinese Academy of Sciences. 61 records from Range table from planktonic foraminifers in ODP Hole 172-1060A. 1882380 records from EURISCO, The European Genetic Resources Search Catalogue. 199 records from Occurrence data of Ectyphus and Parectyphus (Diptera: Asiloidea: Mydidae). 6907832 records from The New York Botanical Garden Herbarium (NY). 1485 records from Richard Staniforth Herbarium (UWPG). 146 records from BIRDRACE Stuttgart 100 trööt. 67786 records from Naturalis Biodiversity Center (NL) - Paleobotany. 4 records from (Table 3) Mean plasma lipid content, and plasma PCB and OH-PCB concentration of polar bear (Ursus maritimus) mothers and cubs. 258966 records from Institut Botanic de Barcelona (IBB-CSIC-ICUB), BC-Plantae. 405 records from Total foraminifera counts of multinet M12/3_MSN561. 170 records from The occurrence and distribution of Najas flexilis (Slender naiad) in Loch of Craiglush, Loch of the Lowes and Loch of Butterstone. 119280 records from Collection Arachnology SMF. 442 records from Mokihinui project: landslide lakes. 2 records from Discovery of a new millipede species in northern Vietnam, and the proposal of a new genus, Parariukiaria (Diplopoda, Polydesmida, Xystodesmidae). 2750 records from Banco de información sobre características tecnológicas de maderas mexicanas. 9946 records from Data from CRSN herbarium digitization initiative under BID-funded project. 3 records from Mammalia (SMNH-MM). 1424 records from Polychaetes in surface sediments off Sylt collected during HEINCKE cruise HE206. 1248 records from Nannofossil abundance of Hole 94-609B. 63418 records from PPEAO - Pêches scientifiques. Peuplements de poissons des écosystèmes estuariens, lagunaires et continentaux d'Afrique de l'Ouest. 5720 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Aves (MFA-ZV-Or). 31 records from Analyses of the recent components in the sand fraction of sediment core PS1220-3. 132 records from Total foraminifera counts of multinet M21/4_MSN721. 7 records from To the revision of the genus Thionia Stål (Hemiptera, Fulgoroidea, Issidae), with description of new genera and new subtribe. 5890 records from (Appendix A) Benthic foraminiferal assemblages in sediments of the last 550 kyr of ODP Hole 130-807A from the Ontong Java Plateau, Pacific Ocean. 7 records from Range table from planktonic foraminifers in ODP Hole 174-1072A. 1146 records from (Table 2) Lithic grain and foraminifera shell counts in sediment core SU90-08. 364599 records from Vascular Plant Collection - University of Washington Herbarium (WTU). 147 records from Measurements of elephant tusk trophies taken in Botswana 2004. 6 records from A new species of Deltaspis Audinet-Serville (Coleoptera: Cerambycidae: Cerambycinae) from Mexico. 36 records from Assemblage of living benthic foraminifera in sediment core CD145_55808#3, >150 µm. 4 records from Three new species of Corynoneura Winnertz from Oriental China (Diptera: Chironomidae: Orthocladiinae). 4 records from A new species of the endemic Australian genus Hyptiogaster Kieffer (Hymenoptera: Gasteruptiidae). 351 records from (Table 10) Planktonic foraminifer abundance of ODP Site 162-986. 1118 records from Herbario MAIA, colección Manuel Martín Bolaños. 38110 records from Akita Prefectural Museum, Insect Collection. 23196 records from Freshwater Diversity Identification for Europe (FREDIE) - funded by the German Leibniz association ( SAW-2011-ZFMK-3). 1058603 records from ECNASAP - East Coast North America Strategic Assessment. 431646 records from Dry Tortugas Reef Visual Census 2006. 10514 records from Données naturalistes de Philippe GOURDAIN. 39566 records from Données sur la chasse Parc amazonien de Guyane. 90 records from The goblin spider genus Ischnothyreus (Araneae, Oonopidae) in Java and Sumatra. 226 records from Biological data measured on water bottle sampels at station AT_II-119/5_26-4. 254 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/014-4. 70 records from Bacteria from Penguin Guano, Antarctica. 2 records from A new species of the genus Comidoblemmus Storozhenko & Paik (Orthoptera: Gryllidae) from Xizang, China. 105 records from BIRDRACE Die Kartoffelsäcke. 6036 records from Fishes in MZNA-VERT: distribution of freshwater blenny in the Segre and Susia rivers (Spain). 1 records from A new species of the genus Leptolalax (Anura: Megophryidae) from Guangxi, China. 950 records from Planktic foraminifera abundance of Hole 23-220. 26 records from Lerneca inalata beripocone subsp. nov. (Orthoptera: Phalangopsidae; Luzarinae): a new taxon for the northern Pantanal of Brazil. 1032 records from Base de données Pecheker. MNHN - DEPARTEMENT MILIEUX PEUPLEMENTS AQUATIQUES. Supplément. 562 records from Nannofossil abundance of Hole 26-254. 27 records from Analyses of the recent components of sediment core PS1012-1. 102 records from (Table 11) Distribution of calcareous nannoplankton in selected samples of ODP Hole 112-687A. 28 records from Nano and microzooplankton abundance and biomass at station NBP97-01-10-2. 21290 records from Sukkulentensammlung Zürich. 6 records from Note su alcune specie di chilopodi della regione palestinese. 1380 records from (Table 2) Distribution of planktonic foraminifers in ODP Site 126-790. 957 records from Artenvielfalt im Rhein-Neckar-Raum. 8212 records from Capture Mark Recapture Data for Scottish Elasmobranchs: 2009-2018. 5221037 records from New South Wales Bird Atlassers. 10349 records from Bacteria Collection in BCRC. 98 records from Seawater carbonate chemistry and biological processes of coccolithophore (Gephyrocapsa oceanica and Coccolithus pelagicus ssp. braarudii) during experiments, 2011. 2086 records from The Ecology of the Inshore Marine Zooplankton of the Chukchi Sea near Point Barrow, Alaska. 6 records from The discovery of the spider genus Putaoa (Araneae, Pimoidae) in Taiwan with the description of a new species, including its web architecture. 3069 records from (Appendix A3) Relative abundances of benthic foraminifera and stable carbon isotope ratios of Nuttallides truempyi at the Paleocene-Eocene thermal maximum in ODP Hole 198-1212B in the central Pacific. 170 records from Nannofossil abundance of Hole 16-157. 240 records from Invertebrados y aves playeras de la Laguna Madre de Tamaulipas, México. 96774 records from Herbarium of Namur. 202 records from Range table from nannofossils in ODP Hole 139-855A. 12 records from A new species, genus and tribe of Sapotaceae, endemic to Madagascar. 24 records from Taxonomic review of the rare Mexican snake genus Chersodromus (Serpentes: Dipsadidae), with the description of two new species. 292 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-51. 9 records from Urogymnus acanthobothrium sp. nov., a new euryhaline whipray (Myliobatiformes: Dasyatidae) from Australia and Papua New Guinea. 12 records from Scapanoclypeus bicoloratus new species from Hardap, Namibia (Coleoptera: Scarabaeidae: Melolonthinae: Tanyproctini). 116 records from Planktic foraminifera abundance of Hole 18-177. 15746 records from Bedfordshire Himalayan Balsam Surveys (WT) - 2010-2012. 268 records from Benthic macrofauna abundance of subcores of sediment core 12930-084. 11021 records from Distribution and abundance of different bat species in the interior of Arabuko-Sokoke Forest and adjacent farmlands in Gede, Kilifi County, Kenya. 6 records from Guilielmia Weise, a little known Afrotropical flea beetle genus: systematic affinities and description of a second new species from Central Africa (Coleoptera, Chrysomelidae, Galerucinae, Alticini). 6 records from Gephyrocharax machadoi, a new species of Stevardiinae (Characiformes: Characidae) from the Rio Paraguai basin, central Brazil. 86 records from Relative abundance of planktic foraminifer Globigerinita uvula in sediment core PS1243-1. 28 records from Benthic macrofauna abundance of sediment core 13077-023. 5282 records from (Table 3) Cretacoeus calcareous nannofossils from ODP Hole 123-766A. 824 records from Crustacean specimens of Kaizuka City Museum of Natural History. 132 records from Nematode densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC09. 13 records from New record of Castanopsides falkovitshi Kerzhner from Korea (Heteroptera: Miridae: Mirinae: Mirini). 770 records from Biodiversidad íctica de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 22 records from Waldgebiet Todtnau- Sonnhalde. 120 records from The ant genus Linepithema (Formicidae: Dolichoderinae) in Colombia. 198 records from MOLLUSQUES DES MANGROVES ET DES ZONES HUMIDES DU SUD TOGO. 7175 records from Collection Crustacea - SNSD. 5496 records from Epibionts on Caribbean mangrove roots from Morrocoy National Park and La Restinga Lagoon National Park, Venezuela. 328 records from Great Eastern Ranges - Southern Highlands. 294 records from (Table 1) Abundance of unicellular eukaryotes in ice cores collected during the July 2008 CCGS Amundsen cruise in Darnley Bay. 407 records from Planktic foraminifera distribution of sediment core TRI172-22. 1008 records from Ants on Nukunonu atoll in 2011. 174286 records from Sheffield Bird Study Group (Yorkshire records). 56 records from Range table from planktonic foraminifers in ODP Hole 139-858B. 658 records from forest_soil_fauna_densities_grouplevel_2008. 421 records from Total foraminifera counts of multinet M21/3_MSN661. 1748 records from Gaïadomo_2017_12_18. 6 records from Odontotrypes (Odontotrupes) tawangensis new species (Coleoptera: Geotrupidae) from Arunachal Pradesh, India. 3496 records from PAMP-tracheo: Vascular plants in Ribera Occidental de Navarra (Spain). PhD project, L. Garde. 24 records from Chenopodieae. 838 records from Colección Thomas G. Zoebisch asociada a la Colección Entomológica del Centro de Estudios en Zoología. 960 records from Bird specimens of Takatsuki Nature Museum (Aquapia Akutagawa). 336 records from Nannofossil abundance of Hole 10-90. 40 records from (Table 1) Early Miocene and late Oligocene ostracods in sediment core CRP-2A. 125 records from Schafheide im Böblinger Wald. 23 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-IR50. 1798 records from NE Scotland marine mammal records 1800-2010. 83 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/313-1. 4481 records from (Table 12A) Occurrences of planktonic foraminifers in selected samples of DSDP Holes 90-590 and 90-590A. 8 records from A new member of the greater double-collared sunbird complex (Passeriformes: Nectariniidae) from the Eastern Arc Mountains of Africa. 79950 records from Carpatica Operation. 77 records from GEO-Tag am Hohlen Stein. 6255 records from Hormigas de la transición matriz - borde - interior de bosque de Fragmentos de Bosque Seco Tropical del Valle del Cauca. 2 records from Dinámica poblacional de Mammillaria crucigera y Neobuxbaumia macrocephala en la región de Tehuacán-Cuicatlán. 339484 records from Instituto de Botánica Darwinion. 198 records from Birdrace-Die_EderSeaWatchers_WsndaH!-Waldeck/Frankenberg. 580663 records from AMNH Mammal Collections. 1430 records from Phytoplankton abundance in surface water in November 1997, Chimbote, Peru. 2679 records from (Table 1) Occurrence and abundance of late Early Cretaceous radiolarians at DSDP Hole 62-463. 30 records from Benthic hard-bottom communities abundance at Liliguapi, Paso Comau, Chile, in 2012. 161 records from Orthoptera (Insecta: Tettigonioidea, Pyrgomorphoidea, Acridoidea) of Kafa Biosphere Reserve, Bale Mountains National Park and other areas of conservation interest in Ethiopia. 146 records from Matter enrichment of the macrofauna community of MAC station 13200-005. 4 records from A new species of the genus Aristochroa Tschitscherine, 1898 (Coleoptera, Carabidae, Pterostichini) from Yunnan, China. 405 records from Tawi Tawi, Philippines Reef Fishes. 6 records from Surveys of beavers in the Rivers Balvag, Leny and Teith in 2012. 500 records from Plant (HBBG-PL). 1605539 records from BRERC species records within last 15 years. 4 records from A new species of the Chinese endemic genus Sinhomidia (Collembola: Entomobryinae) described and the first description of amale of Sinhomidia bicolor. 1879 records from (Table 2) Distribution of planktonic foraminifera in the larger size fraction of ODP Hole 120-747A. 2 records from Il popolamento dell'Appennino meridionale: dall'Appennino campano alle serre calabre. Osservazioni sui chilopodi dell'Appennino lucano e calabrese (Chilopoda). 136 records from Escarabajos estercoleros (Coleoptera: Scarabaeinae) asociados a dos fincas ganaderas de Rionegro, Antioquia (Colombia). 28 records from Description of four new genera and five new species of cicadas from New Caledonia (Insecta: Hemiptera, Cicadoidea, Cicadidae). 6 records from Amphibiens filet/Comcom Chardon Lorrain. 419572 records from WFVZ Bird Collections. 3 records from Planktic foraminifera counts of multinet M21/5_MSN728. 2 records from Ephuta icema Casal, 1969 and its host Auplopus subaurarius Dreisbach, 1963 (Hymenoptera: Mutillidae, Pompilidae) from Brazil. 117 records from Muskox Abundance. 158 records from Umgebung von Schorndorf. 24 records from A review of the genus Haemonides Hübner, [1819] (Lepidoptera: Castniidae). 21 records from (Table 1) Dinoflagellate species and specimen abundance in Maastrichtian sediments of the Bass River Section in the southern New Jersey. 498 records from Range table from benthic foraminifers in ODP Hole 171-1051A. 327 records from MEXU/Frutos y Semillas. 10007 records from Freshwater fishes of the Western Balkans. 325 records from Abundance of microplanton determined from water bottle samples during AEGAEO cruise LIA-8. 1426 records from (Table 3A) Occurrence and estimated abundance of planktonic foraminifers at DSDP Holes 85-572 and 85-572A. 8 records from Dinoflagellate abundance of Hole 81-554A. 89 records from CeDoc de Biodiversitat Vegetal: BCB-bryo. 200149 records from SPF - Herbário da Universidade de São Paulo. 2 records from Arthropoden aus südostalpinen Höhlen.. 26 records from European species of the Gnaphosa alpica complex (Araneae, Gnaphosidae). 1 records from Taxonomy of the Phyllotis osilae species group in Argentina; the status of the “ Rata de los nogales ” (Phyllotis nogalaris Thomas, 1921; Rodentia: Cricetidae). 78 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_15-CTD152. 24998 records from WhiteSeaPlankton. 198384 records from Taiwan Moth Occurrence Data Collected From Social Network. 2808 records from (Table 3) Percentages of planktonic foraminiferal species and varieties from the sediment surface samples from the South China Sea. 4 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 2 records from Additional records of Elasmopus vachoni Mateus & Mateus, 1966 (Crustacea: Amphipoda: Maeridae) from European waters (Tarifa, southern Spain). 612 records from Lice (Phthiraptera) of Ireland. 50 records from Abundance of birds on the channels of Lena Delta in the nesting period. 82 records from A new species and a new subspecies of Euplexia Stephens, 1829 (Lepidoptera: Noctuidae: Xyleninae) from China. 260 records from (Table 3) Palynomorph concentrations for ODP Site 105-645. 711 records from (Appendix B) Abundance of calcareous dinoflagellates of sediment core GeoB1105-4. 16 records from Données naturalistes d'Arnaud BELLANGER. 736 records from Auswildlife. 27924 records from Insect (NSMK-IN). 4 records from First description of the larva and pupa of the coconut palm borer Homalinotus depressus (Linnaeus, 1758) (Coleoptera: Curculionidae: Molytinae) and a discussion about the terminology for immature forms. 471163 records from HUEFS - Herbario da Universidade Estadual de Feira de Santana. 2 records from Synonymic notes in the genus Chlaenius Bonelli, 1810 (Coleoptera: Carabidae: Chlaeniini). 160 records from Taxonomic review of the species of Andrenosoma (Diptera: Asilidae) in Spain and description of a new species. 939 records from Nannofossil abundance of Hole 37-332A. 18 records from Description of Panagrellus ulmi sp. n. (Rhabditida, Panagrolaimidae) from Iran, and comments on the species of the genus and its relatives. 94 records from Queensland Microalgae Collection Database of Identified Species. 364 records from Abundance of planktic foraminifera at CTD station M39/4_361CTD-18. 8 records from Further study on Rhopobota Lederer (Lepidoptera: Tortricidae: Olethreutinae) from China. 639 records from "Phytoplankton and Zooplankton data collected during the Black Sea cruises of UkrSCES R/V Viktor Bugaev 1993". 294 records from Notes on Shore Flies (Diptera: Ephydridae) from Finland and north-western Russia. 3904 records from Phytoplankton abundance in surface water in October 1997, Ilo Peru. 116 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2143-1. 912 records from Øvre Heimdalsvatn, Radiocaesium (Cs-137) monitored annually in brown trout (Salmo trutta). 74134 records from CSIRO Ichthyology provider for OZCAM. 2079 records from (Appendix 2-3) Distribution of planktonic foraminifera in late Neogene sediments of DSDP Site 30-289 in the western Pacific Ocean. 41 records from Tab. 3: Stomach contents of Knots of Hazen Camp. 1320 records from CNMA/Colección de Mamíferos de la Estación de Biología Los Tuxtlas. 18 records from A new species of Formicomotes Sevastianov (Acari: Heterostigmata: Dolichocybidae) associated with termites (Isoptera: Termitidae) from Brazil, with redescription of Formicomotes octipes Sevastianov, 1980. 852 records from Diatom abundance measured on water bottle samples at station PS58/088-4. 21 records from (Table 1) Abundance of ciliates, dinoflagellates, nauplii and krill at different stations in the Godthabsfjord. 10 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station SEPTEMBER-1995-D4. 2 records from A new species of Hemidactylus (Squamata: Gekkota: Gekkonidae) from Qara Dagh Mountains, Kurdistan Region, with a key to the genus in Iraq. 714 records from bmhswatsonshellcollection. 8325 records from CeDoc de Biodiversitat Vegetal: BCN- Algues de J. Rodríguez Femenías. 66 records from Taxonomic revision of the Neotropical genus Caenopangonia Kröber, 1930 (Diptera: Tabanidae). 485 records from (Table 7) Benthic foraminifera genera assemblage at DSDP Section 80-548A-22. 2378 records from Saproxylic insects caught in window traps and hatched from polypores in small and large old forests in southern Norway. 100 records from (Table 2) Abundance, preservation, and distribution of calcareous nannofossils in ODP Hole 135-840A. 2568 records from Distribution géographique de quelques espèces invasives du Bénin (Afrique de l'Ouest).. 636 records from Field Study Group of the Dutch Mammal Society (NL) - 2006 - Mammal Survey Galicica National Park, Macedonia. 342 records from Hormigas de hojarasca asociadas a fragmentos de bosque y cafetales de la zona cafetera de Cundinamarca. 3 records from Two new Cambodian semi-aquatic earthworms in the genus Glyphidrilus Horst, 1889 (Oligochaeta, Almidae), based on morphological and molecular data. 14057 records from Casual records for Scottish Wildlife Trust reserves - Verified data. 53 records from Neotype designation for Sphingius thecatus Thorell, 1890, synonymies, new records and descriptions of six new species from Southeast Asia (Araneae, Liocranidae). 36216 records from Jeu de données convention Eurovia-SPN-2012-2016. 170 records from Collection Reptilia fossil SMF. 20 records from The Pinnotheridae of the northeastern Pacific (Alaska to Mexico): zoogeographical remarks and new bivalve hosts (Crustacea, Brachyura, Pinnotheridae). 3062 records from Biogeographic distribution of the Antarctic and Sub-Antarctic brachiopods (living forms). 356 records from Nannofossil abundance of Hole 58-442A. 3 records from Microplankton counts and carbon biomass at station TT007_7-CTD76. 3884 records from Western Australia Museum, Marine Invertebrate Specimens, Ningaloo Reef - Northwest Cape, Northwest Australia, 1952-2004. 2 records from Alloionema californicum n. sp. (Nematoda: Alloionematidae): a new alloionematid from USA. 47706 records from Field Museum of Natural History (Botany) - Historical Photographs of Type Specimens from Berlin (B). 230 records from Observations individuelles. 4 records from Anaxibia folia spec. nov. - a new litter-dwelling dictynid spider from India (Araneae: Dictynidae: Dictyninae). 12 records from (Table 1) Biomass of cysts and active infusoria in the surface layer of the Central Indian Ocean. 108 records from The Jordan theropod (Maastrichtian, Montana, U. S. A.) referred to the genus Aublysodon.. 3 records from Barsine deliciosa, a new species from China (Lepidoptera, Erebidae, Arctiinae). 103996 records from Herbario Amazónico Colombiano. 2124 records from (Table T1) Planktonic foraminifera abundance of ODP Site 170-1039 sediments. 4 records from Papakula and Hesydrimorpha: how two spider genera were described from the same species collected from the same locality (Araneae: Pisauridae). 2 records from Discovery of the subfamily Rhopalomutillinae (Hymenoptera: Mutillidae) in China and description of Pherotilla brothersi sp. nov.. 214 records from Nannofossil abundance of Hole 73-521. 10847 records from Flora y datos básicos para la evaluación de las actividades apícola y forestal en tres áreas focales del corredor Sian Ka'an-Calakmul. 2 records from Graureiher in Lans. 1533 records from Diversidad y distribución de las comunidades de fitoplancton y peces de ríos y lagunas del volcán San Martín de la reserva de la biósfera Los Tuxtlas. 81 records from (Appendix 1) DSDP Site 94-607A ostracode species census data. 2 records from Murcia ephippiata. 9888 records from DVPR - Herbário da Universidade Tecnológica Federal do Paraná - Dois Vizinhos. 8352 records from Badger and Habitats Survey of Ireland. 7158 records from North East Scotland Mosses and Liverworts (1950-2014). 42 records from New and remarkable leafhoppers and planthoppers (Hemiptera: Auchenorrhyncha) from Switzerland. 80 records from Abundance and carbon biomass of phytoplankton at station TT007_5-CTD51. 1614 records from Database about reference specimens for medicinal plants, in the Apocynaceae family, owned by CNARP. 210017 records from Invert Paleo Specimens. 87 records from (Tab. 11) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 32-304, Japanese Magnetic Lineations east of Japan. 3926 records from Hypogean macro-Crustacea records. 1072 records from 10. GEO - Tag der Artenvielfalt 2008 - LSG "Pfarrhübel" Chemnitz. 592 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Rallidae. 430 records from Rescate de epífitas Oleoducto Bicentenario, Tramo Araguaney - Banadía (forofitos). 228 records from Range table from planktonic foraminifers in ODP Hole 182-1129D. 2 records from A new species of the phyline plant bug genus Chimairacoris from central Sulawesi, Indonesia (Hemiptera: Heteroptera: Miridae: Phylinae). 10 records from Neoclita pringlei (Scarabaeidae, Cetoniinae), a new relict genus and species from the Drakensberg Range of South Africa. 6 records from Bryochoerus liupanensis sp. nov. and Pseudechiniscus chengi. sp. nov. (Tardigrada: Heterotardigrada: Echiniscidae) from China. 46 records from New data on the genus Domene (Coleoptera: Staphylinidae: Paederinae) of mainland China. 53292 records from IMOS - AusCPR: Zooplankton Abundance. 309 records from Plasm bearing foraminifera counts of multinet POS200/6_MSN837. 11 records from Specimens of Huffmanela lusitana of the Collection of Pathology of IPMA. 1528 records from Centre d'Estudis Avançats de Blanes. Limnological Observatory of the Pyrenees - Fitoplancton de lagos pirenaicos. 41 records from Revision of the genus Metaterpna Yazaki, 1992 (Lepidoptera, Geometridae, Geometrinae), with description of a new species from China. 178 records from (Tab. 9.B) Presence and abundance of benthic fauna at station FINO 1 in 2005-2007. 50 records from Leben in den Elbwiesen. 9 records from Mimogonellus dreybrodti sp. n., a new cave-inhabiting Osoriinae from Laos (Coleoptera: Staphylinidae). 27 records from Cleaning old cabinets: revealing the taxonomy of Sri Lankan wolf spiders (Araneae, Udubidae and Zoropsidae). 167 records from (Data S1) Palynology of ODP Site 113-696. 3702 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Pisces_Types. 230 records from Range table from benthic foraminifers in ODP Hole 149-899B. 2122 records from Antarctic Biodiversity Studies 2006 (Ross Sea, Scott Island, and Balleny Islands) (TAN0602). 97085 records from MSB Bird Collection (Arctos). 24261 records from Naturhistorisches Museum Mainz, Zoological Collection. 10 records from Coleophora meridiogallica Baldizzone, Huemer & Nel, sp. n. from France (Lepidoptera, Coleophoridae). 1435 records from Zukünftiges NSG Höftland/Bockholmwik. 2 records from Arthropoden aus südostalpinen Höhlen.. 293225 records from Ichthyology Collection - Royal Ontario Museum. 50 records from Revision of African Apiocera (Diptera: Apioceridae). 8874 records from (Table 6) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-708A. 66 records from Phytoplankton abundance at station Rigel_5_2005-03 in March 2005, Chipana, Chile. 38 records from Registro Herpetofauna de los Corregimientos de Juanchaco y Ladrilleros, Municipio de Buenaventura (Valle del Cauca) Septiembre de 2016. 1 records from Tapantiomyia enigmatica, new genus and species proposed for a stilt-legged and otherwise bizarre coenosiine fly (Diptera: Muscidae) from Costa Rica. 11171 records from Diversidad bentónica de la laguna Celestún, Yucatán. 6985285 records from Other BSBI Scottish data up to 2012. 902 records from Données naturalistes acquises sur les sites du MNHN, en particulier du Jardin des plantes et de l'ilôt Poliveau. 48242 records from Endemic plants of the Congo basin. 6 records from Atlas de la flore de la forêt du Madrillet. 17031 records from European Invertebrate Survey (EIS-NL) - Orthoptera Specimen. 7145 records from RAVON (NL) - Network Ecological Monitoring Reptiles. 4 records from A new species and phylogenetic insights in Hesiospina (Annelida, Hesionidae). 206910 records from ANTAVIA-TrackingKing. 170 records from CSIRO, Cruise SS200803, Marine Biological Survey, Great Australian Bight; South Australian and Tasmanian continental slope, 2008. 1734 records from (Appendix 2, Table 4) Relative abundances of benthic foraminifera in Late Quaternary sediments of ODP Hole 122-762B in the southeast Indian Ocean. 1586 records from (Table 2) Neogene benthic foraminifers of ODP Hole 120-748B. 2 records from Planktic foraminifera abundance of Hole 8-71. 918 records from Dinoflagellate cysts from sediment core PS2138-1. 16 records from Description of four new species of Ochlerini from South America (Hemiptera: Pentatomidae: Discocephalinae). 8 records from A new Agraecina spider species from the Balkan Peninsula (FYR Macedonia) (Araneae: Liocranidae). 8248 records from Herbario de la Universidad de La Laguna:TFC-Bry. 1602 records from Société_du_Canal_de_Provence_2017_12_18. 32354 records from EFC - Herbário Escola de Florestas Curitiba. 22600 records from Eastern Canada Benthic Macro Fauna (OBIS Canada). 34 records from NCC Berkshire Rare Plant Surveys 1985-1987. 198 records from The genus Dichopygina gen. n. (Diptera: Sciaridae). 51092 records from Museo Nacional de Ciencias Naturales, Entomología. 88 records from (Table 2) Planktonic foraminifer abundance of ODP Hole 162-907B. 211 records from Schulgarten Hans-Carossa-Oberschule. 4 records from Range extension of the rare braconine genus, Lyricibracon Quicke (Hymenoptera: Braconidae), with the description of a new species from India. 55 records from A review of the families and genera of the superfamily PLATYSCELOIDEA Bowman & Gruner, 1973 (Crustacea: Amphipoda: Hyperiidea), together with keys to the families, genera and species. 4 records from A new species of the genus Xysticus C. L. Koch from Turkey (Araneae: Thomisidae). 1576 records from Checklist of Cerambycidae, Disteniidae and Vesperidae (Coleoptera) primary types of the Museu de Zoologia, Universidade de São Paulo, São Paulo, Brazil. 4 records from Stadtrand Berlin - Altglienicke/ Was krabbelt auf unserem Abenteuerspielplatz?. 342 records from (Table 6) Relative abundance of benthic foraminifera in ODP Hole 112-687A. 1666 records from Planktic foraminifera abundance of Hole 33-315A. 24120 records from UCM Bird Collection (Arctos). 2049 records from Planktic foraminifera counts during POLARSTERN cruise ARK-XI/1. 908 records from DREAL_PACA_-_N2000_-_CEN_PACA_2017_12_18. 63 records from SuLaMa yam occurence data. 52806 records from EWT: African Crane Conservation Programme Sightings. 67 records from Early-diverging bumblebees from across the roof of the world: the high-mountain subgenus Mendacibombus revised from species’ gene coalescents and morphology (Hymenoptera, Apidae). 410 records from (Table 5) Absolute abundances of planktonic foraminifera in Maastrichtian to upper Thanetian sediments of DSDP Hole 43-384. 70 records from New species of leaf-mining Nepticulidae (Lepidoptera) from the Neotropical and Ando-Patagonian regions, with new data on host plants. 100041 records from Coleção de Entomologia do Laboratório de Biologia Vegetal. 32 records from Abundance of microplankton from bottle APRIL-2000-K2. 231 records from An update on the spider genus Loxosceles (Araneae: Sicariidae) in the Afrotropical region, with description of seven new species. 120000 records from Birds (NSMK-BI). 9789 records from Danish True Bugs. 1212 records from (Table 17) Calcareous nannofossil occurrences in ODP Hole 130-804C. 9608 records from Species within North Ayrshire from 1984 - Present. 16016 records from Field Survey. 78 records from Südpark (Bochum-Wattenscheid). 2 records from A new species of gecko (Squamata: Diplodactylidae: Strophurus) from central Queensland, Australia. 623209 records from Natural History Museum, University of Tartu. 86 records from Dinoflagellate abundance of Hole 14-137. 292 records from DREAL_PACA_-_N2000_-_Syndicat_Mixte_du_Bassin_des_Sorgues_2017_12_18. 116 records from SuLaMa plant monitoring. 8 records from Diaphanosoma Fischer, 1850 (Crustacea: Cladocera: Sididae) of Lake Turkana (East Africa), with the description of a new species of the genus. 11 records from New species of Neotropical Acanthocinini (Coleoptera, Cerambycidae, Lamiinae). 32 records from Microzooplankton abundance and biomass at station NBP97-08-32-1. 447 records from Orthoptera del Museo de Entomología de la Universidad del Valle. 6 records from First report of the genus Conostigmus Dahlbom (Hymenoptera: Ceraphronoidea: Megaspilidae) from India with description of a new species. 644 records from Données naturalistes de Pierre NOEL (stage). 1641 records from RMT Trawl catch from the 2003/04 V3 BROKE-West voyage. 1930 records from Nature Conservancy Council Oxfordshire Fen Survey 1983 (as held by Thames Valley Environmental Records Centre). 120 records from Macrofauna biomass in surface sediment sampled during cruise DI237. 102 records from Landschaftsschutzgebiet Schmutterwald. 1490 records from Nannofossil abundance of Hole 94-611. 56 records from Mastofauna presente en el Alto del Buey, Bahía Solano, Chocó. 70948 records from Données naturalistes de Thomas GAILLARD. 12292 records from Diversité des espèces menacées des zones classées et terroirs villageois du Bénin (Afrique de l'Ouest).. 742 records from Foraminifera abundance of Hole 39-356. 1518 records from Distribution of planktic foraminifera of sediment trap NB7. 101414 records from The Vascular Plant Collection at the Botanische Staatssammlung München. 15 records from Inventario de Herpetología Buenos Aires, Tauramena, Casanare. 6 records from Occurrence of mammalia relicts at site Vjetrenica Höhle. 9 records from A new stygobiont species of Halocaridinides Fujino & Shokita, 1975 (Crustacea, Decapoda, Caridea, Atyidae) from caves on Socotra Island (Yemen), with notes on the genus. 2 records from A new species of Frankliniella with 7 - segmented antennae from Mexico (Thysanoptera, Thripinae). 434 records from Abundance of coccosphere-units of site GIK23414. 549 records from The Wildlife Information Centre - BioBlitz Events. 3 records from Description of a new genus of Elaphidiini with two new species (Coleoptera, Cerambycidae, Cerambycinae). 1892 records from English Nature Berkshire SSSI Records. 88 records from Pollen analysis of surface samples near sediment core Fiekers Busch. 9621 records from UAFMC Herps. 394 records from Nannofossil abundance of Hole 19-192. 2990 records from Insectos en el municipio de Medina, Cundinamarca - Proyecto Colombia Bio. 146 records from Taxonomic revision of the sub-Saharan Anthidiellum Cockerell (Apoidea: Megachilidae: Anthidiini). 3 records from Irene litanga, a new genus and new species in the Polia generic-complex from China (Lepidoptera, Noctuidae, Hadeninae, Hadenini). 16 records from Analyses of the recent components of sediment core PS1278-1. 6 records from Type designations and taxonomic remarks for Nearctic sap beetles in the subfamily Carpophilinae Erichson (Coleoptera: Nitidulidae). 7080 records from Données bibliographique de la base BOMBINA. 274 records from Range table from benthic foraminifers in ODP Hole 182-1126D. 101135 records from Raptors of the World. 20 records from Feuchtwiesen Wippertal bei Wippra. 1782144 records from Vegetation data from protected areas in Denmark (§ 3 in the Danish Nature Protection Act). 20 records from Microzooplankton abundance and biomass at station TT054_24-21. 1152585 records from Dry Tortugas Reef Visual Census 2012. 990 records from Fauna asociada (endocárstica) a cuevas en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 2472 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO-Algae. 8 records from New data on recently described rodent species Paulina's Limestone Rat Saxatilomys paulinae Musser, Smith, Robinson & Lunde, 2005 (Mammalia: Rodentia). 198 records from (Table 1) Distribution of planktonic foraminifers in ODP Hole 125-786A. 1302 records from Elasmobranquios del sistema laguna Chantuto-Panzacola y Carretas-Pereyra de la Reserva de la Biósfera La Encrucijada, Chiapas. 1081413 records from Stuart M. Fullerton Collection of Arthropods (UCFC), University of Central Florida. 67766 records from Vegetation surveys of coastal shingle in Great Britain. 1 records from Confirmation of the identity of the type host of the louse Halipeurus fallacis (Phthiraptera: Philopteridae). 820 records from Diatom abundance measured on water bottle samples at station PS58/012-5. 2 records from Opamyrma hungvuong, a new genus and species of ant related to Apomyrma (Hymenoptera: Formicidae: Amblyoponinae). 190 records from Données naturalistes de Lucile VOURZAY. 1 records from Clarification of the identity of Helicina mediana Gassies, 1870 from New Caledonia (Gastropoda, Neritimorpha, Helicinidae). 580542 records from Bee Biology and Systematics Laboratory. 375 records from Relative abundance of dead benthic foraminifera in East Atlantic surface sediments off Senegal and Gambia (Table 2). 24 records from Additions to the Indonesian crab fauna of the genus Mariaplax Rahayu & Ng, 2014, and notes on Hexapus timika Rahayu & Ng, 2014 (Crustacea, Decapoda, Brachyura, Hexapodidae). 231 records from Planktic foraminifera counts at CTD station M39/4_404CTD-57. 63 records from Höhle am Neuweg / Sächsische Schweiz. 553 records from Range table from benthic foraminifers in ODP Hole 198-1208A. 2861 records from Insect Arthropods (KIDR-IN). 68393 records from FURB - Herbário Dr. Roberto Miguel Klein. 1485 records from Life Science National Tsing Hua University. 13 records from Occurrence of mammalia relicts at site Endingen. 129 records from Total foraminifera counts of trap L2_96_62. 16 records from Two new Oedanomerus species from Zimbabwe (Coleoptera: Scarabaeidae: Melolonthinae: Tanyproctini). 116654 records from Inventaire National du Patrimoine Naturel : Fichier communal des ongulés. 3496 records from Siliceous microfossil occurrence, Site 177-1094. 28995 records from vegetation releves on grassland gridplots 2007-2009. 674 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Falconidae. 4350 records from Invasión de Pinus spp y la conservación de la diversidad florística en Los Altos de Chiapas, México. 244 records from Peces de agua dulce del municipio El Carmen de Chucurí, Santander - Proyecto Santander BIO. 2 records from Chilopoden und Diplopoden aus Jugoslavischen Höhlen. 118 records from Macrofauna biomass in surface sediment sampled during cruise DI222/2. 138 records from New records of Orussus minutus Middlekauff, 1983 (Hymenoptera: Orussidae) represent a significant western range expansion. 4359 records from Inventario Florístico de la Reserva de la Biósfera La Sepultura del Corredor Biológico Sierra Madre del Sur. Fase II. 693 records from (Figure 2e) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3205. 47235 records from Museu de Ciències Naturals de Barcelona: MCNB-Art. 22 records from Planktic foraminifera abundance of Hole 47-398B. 14836 records from Base de données Pecheker (modifiée). Museum National D'Histoire Naturelle - DEPARTEMENT MILIEUX PEUPLEMENTS AQUATIQUES. 918 records from Colección de Entomología - Coleoptera - Chrysomeloidea. 2 records from Chalcogenia brandli sp. nov. from Ethiopia (Coleoptera: Buprestidae: Anthaxiini). 7 records from A new species of Sphelodon Townes (Hymenoptera: Ichneumonidae: Banchinae) from Colombia. 402 records from Planktic foraminifera abundance of Hole 4-31. 7360 records from Morandin PhD Thesis / La Crete, Alberta. 1420 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 2005-2006. Part 1. 4196 records from (Appendix Table 1) Absolute abundances of benthic foraminifers in DSDP Hole 94-608. 1098 records from (Table 8) Distribution of planktonic foraminifers in ODP Hole 108-661A. 100 records from Collection Crustacea - PUM. 6830 records from Plant Specimens collections of the Kyushu University Museum. 2 records from A new species of Priochilus Banks, 1944 (Hymenoptera, Pompilidae, Pompilinae) from Panama. 3 records from Late Cretaceous species of Vologesia (Echinoidea, Cassiduloida) from northern Spain. 87681 records from VIS - Fishes in estuarine waters in Flanders, Belgium. 224 records from Taxonomic review of the genus Leucopholis Dejean, 1833 (Coleoptera: Scarabaeidae: Melolonthinae: Leucopholini) in the Philippines. 101480 records from River macroinvertebrate data for 2005 and 2006. 25 records from Boreonemoral regnskog i Sveio. 2 records from Range table from planktonic foraminifers in ODP Hole 144-874A. 3 records from Aplectana nordestina n. sp. (Nematoda: Cosmocercidae) parasitizing Leposternon polystegum (Squamata: Amphisbaenidae) from Northeastern, Brazil. 208520 records from Herbario de Plantas Vasculares de la Universidad de Salamanca: SALA. 212 records from East Weddell Sea echinoids from the JR275 expedition. 8196 records from Formicidae Collection Univesity of Granada. 154244 records from Lepidoptera (Rhopalocera y Heterocera) de áreas prioritarias para la conservación en la Península de Yucatán, con registros de adultos y estados inmaduros. 284 records from Total foraminifera counts of multinet POS247/2_MSN1385. 8 records from After seventy-seven years Ptiloneuropsis Roesler (Psocodea: Psocomorpha: Ptiloneuridae) ceases to be a monotypic genus: a new species from Bahia, Brazil. 172 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 199 records from Occurrence data of Laphyctis (Diptera: Asiloidea: Asilidae). 1386340 records from Bernice P. Bishop Museum. 408 records from Phytoplankton abundance at several stations in December 2004, Chipana, Chile. 13255 records from Tetraonid line transect surveys from Norway: Data from Statskog. 19 records from Descriptions of three new species of the harvestmen genus Pseudogagrella (Opiliones: Sclerosomatidae: Gagrellinae) from Taiwan, supported by morphological and molecular evidence. 242 records from Range table from planktonic foraminifers in ODP Hole 167-1022A. 33 records from (Appendix 2) Abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core SU81-18. 3 records from Barsine amaculata, a new species from Vietnam (Lepidoptera, Erebidae, Arctiinae). 1174 records from Collection Tunicata SMF. 63 records from Redescription of two troglobiotic species of Deuteraphorura Absolon, 1901 (Collembola, Onychiuridae) from the Western Carpathians. 1 records from New carnivorous dinosaur from the Lance formation of Montana. 1394 records from Range table from planktonic foraminifers in ODP Hole 155-946A. 271 records from (Appendix 3) Calcareous nannofossils in ODP Hole 113-690B. 12469 records from Assemblage of dinoflagellate cysts analysed in sediment core SO78-158-1. 68 records from Range table from benthic foraminifers in ODP Hole 178-1099A. 852 records from Species composition in twelve (12) Afzelia africana Sm & Pers populations in Benin.. 2202 records from Colección de Entomología - Orthoptera. 1477 records from (Table 1) Planktonic foraminiferal communities at DSDP Holes 94-609B and 94-609. 842 records from Marine specimens of Misaki Marine Biological Station, Graduate School of Science, The University of Tokyo. 2728 records from Caracterización de la vegetación en los sectores de Aipe (Huila), Yaví (Tolima) y Dagua (Valle del Cauca), como insumo para la identificación de oportunidades de conservación y la recuperación de servicios ecosistémicos del bosque seco. 20 records from Kita-Wäldchen Fuchsturmweg Jena. 1347 records from Abundance of phytoplankton, heterotrophic nanoflagellates and bacteria through the water column at time series station L4 in the Western English Channel in 2011. 271 records from Herbario de Plantas Vasculares del Museo Municipal de Ciencias Naturales 'Lorenzo Scaglia' MMPEAAH. 314 records from Nannofossil abundance of Hole 18-175. 2206 records from Megaloptera, Raphidioptera, Neuroptera in Upper Silesian Museum entomological collection. 306 records from Ostracoda abundance in DSDP Leg 87 holes. 2398 records from Estudio monográfico de la familia Rhamnaceae en México. 32 records from Avistamiento de Aves Corregimientos de Juanchaco y Ladrilleros, Buenaventura, Valle del Cauca - Septiembre 2016. 1445 records from Planktic foraminifera counts of sediment core V28-127. 18 records from Range table from benthic foraminifers in ODP Hole 144-871A. 493 records from Données naturalistes de Sylvain VRIGNAUD. 17450 records from Fife breeding bird tetrad atlas 1991-99. 90 records from Pseudecheneis maurus, a new species of glyptosternine catfish (Teleostei: Sisoridae) from Central Vietnam.. 60 records from Données naturalistes de Willy CHENEAU. 52 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Thinocoridae. 4636 records from Fundación Miguel Lillo - Colección Ictiológica. 1010 records from Flora vascular de las llanuras aluviales del bajo río Nechí (Antioquia, Colombia). 80 records from The identity of Pseudecheneis sulcata (M'Clelland, 1842), with descriptions of two new species of rheophilic catfish (Teleostei: Sisoridae) from Nepal and China.. 43 records from Range table from nannofossils in ODP Hole 199-1216A. 282 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB06 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms. 14 records from A new species of Trichomycterus (Siluriformes: Trichomycteridae) from south Brazil and redescription of T. iheringi (Eigenmann).. 167 records from Water vole survey of Beinn Eighe National Nature Reserve - October 2011. 306 records from (Table DR1) Biofacies, percentages of important benthic foraminifera and isotope data at ODP Site 758. 804 records from Dinoflagellate abundance of Hole 81-555. 42 records from Nano and microzooplankton abundance and biomass at station NBP97-01-03-7. 10 records from First record of the family Stephanidae (Hymenoptera: Stephanoidea) for the fauna of Saudi Arabia, with the description of a new species. 1910 records from Diversidad y distribución altitudinal de maíces nativos en la región de los Loxicha, Sierra Madre del Sur Oaxaca. 4 records from (Table 1) Preservation of sporomorphs in lithologic units III and IV of ODP Hole 120-750B. 6513 records from Distribution of main calcareous nannofossils at Site 1093. 1 records from A new species of Danothrips from Southwestern China (Thysanoptera: Thripidae). 79 records from Benthic foraminiferal assemblage (dead) in MUC OB10-K, size fraction >150 µm. 38909 records from Museu Paraense Emilio Goeldi - Lepidoptera Collection. 283 records from A multi-proxy investigation of sediment core GeoB7165-1 ~60 km offshore Concepción. 364 records from Schulgelände Paul-Gerhardt-Schule-Dassel. 388 records from fauna_do_municipio_de_araraquara-sp. 8 records from New species and records of Awas Löbl (Coleoptera: Staphylinidae: Pselaphinae) from China, with notes on the biology of the genus. 6990 records from Seaweed (Plantae) Collection of the Seto Marine Biological Laboratory, Kyoto University. 76966 records from Base de datos de aves mexicanas del Natural History Museum, Tring, Inglaterra. 2 records from Cirrhilabrus cyanogularis, a new species of fairy wras
Keywords: GBIF; biodiversity; species occurrences